Open-cell polymer sheet incorporated with nanoparticles

By introducing nanoparticles into the open-pore polymer sheet and utilizing gradient density and electrostatic effects, the problem of high cross-flow pressure drop in the filter in the prior art is solved, and a more efficient filtration effect and cost reduction is achieved.

CN119255861APending Publication Date: 2025-01-03MATIF LUXEMBOURG +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380041756.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-08
Filing Date
2023-04-07
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing open-pore polymer sheet filters have cross-flow pressure drop problems during the filtration process, which leads to an increase in filtration cost and is difficult to effectively reduce the total pressure drop across the support membrane layer.

Method used

Using an open-porous polymer sheet containing nanoparticles, the nanoparticles are arranged in the polymer layer to capture contaminants, and the filtration efficiency is improved through gradient density distribution and electrostatic effects, reducing the total voltage drop.

Benefits of technology

It effectively reduces the total pressure drop of the filter, improves filtration efficiency, reduces operating costs, and improves pollutant capture capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005143783690000401
    Figure BDA0005143783690000401
  • Figure BDA0005143783690000402
    Figure BDA0005143783690000402
  • Figure BDA0005143783690000421
    Figure BDA0005143783690000421
Patent Text Reader

Abstract

Open-cell polymer layers, sheets, webs, or films for a variety of different applications are provided. The polymeric sheet comprises at least one polymeric layer having one or more pores for a gas or liquid to flow therethrough, and a plurality of nanoparticles disposed within the polymeric layer such that the nanoparticles are disposed between a first surface of the polymeric layer and a second surface opposite the first surface. The nanoparticles filter contaminants passing through the polymeric sheet. In certain embodiments, the perforated sheet comprises a support membrane layer in a gas or liquid filter. The nanoparticles reduce the total pressure drop across the support membrane layer to improve the efficiency of such filters.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Application Serial No. 63 / 328,959, filed April 8, 2022, the entire disclosure of which is incorporated herein by reference for all purposes. This application is also related to commonly assigned, co-pending U.S. Provisional Patent Application Serial Nos. 63 / 328,970, 63 / 328,983, 63 / 328,998, 63 / 329,009, 63 / 329,018, 63 / 329,137, 63 / 329,146, 63 / 329,155, 63 / 329,158, 63 / 329,161, and 63 / 329,162, all of which were filed on April 8, 2022, the entire disclosures of which are incorporated herein by reference in their entirety for all purposes. Technical Field

[0003] The present description generally relates to open-cell polymer sheets, support members, and other materials incorporating nanoparticles, and filters formed from such materials. Background Art

[0004] The open-cell polymer sheet or film is a lightweight nonwoven material that includes holes, pores, or perforations. The holes can be embossed into a pattern (e.g., circular, diamond, hexagonal, rectangular, triangular, rectangular, etc.) and then stretched until holes are formed in the thinned regions produced by the embossing. Such open-cell substrates can be formed from a variety of polymers (e.g., polypropylene, polyethylene, high-density polyethylene ("HDPE"), etc.). The polymer layer, for example, can comprise an extruded film.

[0005] Apertured films are used in many applications including finger bandages, surgical gowns, surgical drapes, masks, teeth whitening strips, hydrogel scrims, nasal support materials, electrode support products, filters, food processing, packaging and textile applications, agricultural products, food packaging (e.g., cheese production nets), etc. Apertured films are commercially available and are available in the form of Trademark sales.

[0006] One particularly useful application of open-cell membranes is as a support product for air and liquid filtration devices. Support sheets or membrane layers are often used in filters to provide structural support for the filter layers. These sheets are often open-cell to allow filtrate to pass through the sheets to the filter media below. Typically, when filtering at a given rate, a cross-flow pressure drop across the support membrane can be observed, indicating an increase in the force required to push the fluid through the filter. Minimizing the cross-flow pressure drop across a given support membrane can reduce the operating cost of the filtration.

[0007] Therefore, there is a need for improved supported membrane layers and filters comprising such membrane layers. It is desirable to reduce the overall pressure drop across the supported membrane layer to increase the efficiency of such filters. Summary of the invention

[0008] A brief overview of the claimed subject matter is presented below to provide a basic understanding of some aspects of the claimed subject matter. This summary is not a comprehensive overview of the claimed subject matter. It is neither intended to identify the key or important elements of the claimed subject matter nor to describe the scope of the claimed subject matter. Its sole purpose is to present some concepts of the claimed subject matter in a simplified form as a prelude to the more detailed description presented later.

[0009] Provided is an open-cell polymer layer, sheet, net or membrane comprising one or more holes, pores or perforations and doped with nanoparticles in the polymer layer. In certain embodiments, the open-cell sheet is included in a supported membrane layer in a gas or liquid filter. The open-cell polymer sheet can provide support for the filter medium, for example, or a separate layer can be attached to provide the required structural support. The nanoparticles capture pollutants and reduce the total pressure drop across the supported membrane layer to improve the efficiency of such filters.

[0010] In one aspect, the polymer sheet comprises at least one polymer layer having one or more pores for gas or liquid to flow therethrough, and a plurality of nanoparticles disposed within the polymer layer such that the nanoparticles are disposed between a first surface of the polymer layer and a second surface opposite the first surface. The nanoparticles filter contaminants that pass through the polymer sheet.

[0011] In certain embodiments, the polymer sheet is an extruded film. The hole may include a pore or a perforation. The hole may have any suitable shape, such as a rhombus, a circle, a hexagon, a square or a combination thereof. In certain embodiments, the sheet has a plurality of wrinkles extending across the surface of the polymer layer. Various types of sheets may be combined, and one or more layers may be used. Sheets of different materials may be combined.

[0012] The polymer layer may be selected from the group consisting of polypropylene film, high density polyethylene film and polylactic acid film.The polymer sheet may also comprise a net, mesh, fabric, knit or braid.

[0013] In certain embodiments, the polymer layer is a substantially rigid support layer for a gas filter. In other embodiments, the polymer layer is a flexible surface layer for a face mask. In further embodiments, the polymer layer is a flexible surface layer for a finger bandage pad.

[0014] The polymer layer can be coextruded to form a tacky adhesive layer. The polymer layer can have a first surface and a second surface opposite to the first surface, and the nanoparticles can form a gradient within the polymer layer so that the density of the nanoparticles decreases from the first surface to the second surface. In an embodiment, the nanoparticles are substantially uniformly dispersed throughout the polymer layer.

[0015] In some embodiments, nanoparticles can be added to the substrate from the first and second surfaces. In these embodiments, the surface density or "addition amount" at the first surface and the second surface can be substantially equal to each other, or they can be different depending on the application. In these embodiments, the surface density or "addition amount" present in the middle of the substrate is lower than the surface density or "addition amount" at the outer surface. For example, the surface density in the middle of the substrate can be about 75% of the surface density at the outer surface, or can be about 50%, 40% or 25%.

[0016] In certain embodiments, the nanoparticles may comprise about 0.1 g / m 2 About 20 g / m 2 , preferably at least about 2.0 g / m 2 The specific amount of addition or surface density may depend on the application. For example, the applicant has found that a higher surface density or addition will increase the efficiency of the nonwoven material in filtering pollutants.

[0017] In certain embodiments, nanoparticles have been deposited into the substrate through the first surface. The nanoparticles penetrate into a certain "depth" of the substrate between the first and second surfaces through the first surface. As used herein, the term "at a certain depth" means that the nanoparticles are dispersed across the first surface of the polymer sheet so that at least some of the nanoparticles are arranged between the first and second relative surfaces in the internal structure of the polymer sheet. In other embodiments, the nanoparticles are substantially penetrated throughout the substrate from the first surface to the second surface. In other embodiments, the nanoparticles are dispersed in a portion of the polymer sheet from the first surface to a position between the first and second surfaces. In some embodiments, the nanoparticles penetrate at least 25% of the width or thickness between the first and second surfaces from the first surface, or more preferably at least about 50% of the thickness.

[0018] In some embodiments, the nanoparticles are three-dimensionally distributed in space relative to the supporting fibers, which can increase the fiber surface area and microvolume within the polymer sheet. The three-dimensional distribution can also prevent complete clogging of a specific portion of the anti-polymer sheet, which is particularly useful in filter media because it allows fluids (e.g., air and other gases) to pass through the filter, thereby reducing the overall pressure drop on the filter.

[0019] In certain embodiments, the polymer sheet has a thickness from the first surface to the second surface, wherein the nanoparticles are arranged in the polymer sheet with at least 70% of the width from the first surface to the second surface. In an example, the nanoparticles are arranged in the polymer sheet with at least 90% of the thickness from the first surface to the second surface.

[0020] In certain embodiments, the nanoparticles are isolated in a fluid and dispersed through the first surface of the polymer sheet. For example, the fluid can be a gaseous medium, such as air, helium, nitrogen, oxygen, carbon dioxide, etc. The nanoparticles can be dispersed by this gaseous medium through an air flow, an aerosol, an evaporator, a spray, or other suitable delivery mechanism.

[0021] Nanoparticles can include any suitable material, such as glass, biosoluble glass, ceramic materials, acrylic, carbon, metals (e.g., alumina), polymers (e.g., nylon, polyethylene terephthalate, etc.), polyvinyl chloride (PVC), polyolefins, polyacetals, polyesters, cellulose ethers, polyalkylene sulfides, poly(arylene oxides), polysulfones, modified polysulfone polymers and polyvinyl alcohol, polyamides, polystyrene, polyacrylonitrile, polyvinylidene chloride, polymethyl methacrylate, polyvinylidene fluoride, and any combination thereof.

[0022] The fibers of the substrate can be produced by any method, including but not limited to air-laid, spinneret, gel spinning, melt spinning, wet spinning, dry spinning, island-in-the-sea staple fibers or spunbond, segmented pie staple fibers or spunbond, etc. The cross-section of the contemplated fibers can have a variety of shapes, including but not limited to round, kidney bean, dog bone, trilobal, barbell, bow tie, star, Y, etc.

[0023] The fibers may be man-made or natural. Suitable materials for the fibers include, but are not limited to, polypropylene, polyester (PET), PEN polyester, PCT polyester, polypropylene, PBT polyester, copolyamide, polyethylene, high density polyethylene ("HDPE"), LLDPE, cross-linked polyethylene, polycarbonate, polyacrylate, polyacrylonitrile, polyfumaronitrile, polystyrene, styrene maleic anhydride, polymethylpentene, cyclic olefin copolymers or fluorinated polymers, polytetrafluoroethylene, perfluoroethylene and hexafluoropropylene or copolymers (such as P(VDF-TrFE)) or terpolymers (such as P(VDF- TrFE-CFE)), propylene, polyimide, polyetherketone, cellulose ester, nylon and polyamide, polymethacrylic acid, poly(methyl methacrylate), polyoxymethylene, polysulfonate, acrylic acid, styrenated acrylic acid, pre-oxidized acrylic acid, fluorinated acrylic acid, vinyl acetate, vinyl acrylic acid, ethylene vinyl acetate, styrene-butadiene, ethylene / vinyl chloride, vinyl acetate copolymer, latex, polyester copolymer, carboxylated styrene acrylic or vinyl acetate, epoxy resin, acrylic copolymer, phenolic resin, polyurethane, cellulose, styrene or any combination thereof. Other conventional fiber materials are contemplated.

[0024] The fibers may include fibers of varying sizes, with the fibers typically ranging in diameter from about 1 to 1000 microns and in length from about one-half inch to three inches.

[0025] In certain embodiments, the fiber is a biocomponent fiber having a core and a sheath. In embodiments, the core is not concentric with the sheath. In other embodiments, the core is concentric with the sheath.

[0026] In certain embodiments, the nanoparticles are isolated in the fluid and dispersed by the first surface of the polymer layer. The polymer layer may include fibers with static charge. The nanoparticles are selected from the group consisting of carbon fiber, glass fiber, polypropylene fiber, nylon fiber, polylactic acid fiber and combinations thereof.

[0027] In certain embodiments, polymer sheet (i.e. fiber and / or nanoparticle) can be electrostatically charged, so that, for example, pollutants can be captured by mechanical and electrostatic filtration. The bonding between fiber and nanoparticle can also be enhanced by electrostatically charging nanoparticles, fiber or both. For example, in certain embodiments, fiber is electrostatically charged, so that mechanical filtration can be achieved by nanoparticles, and electrostatic filtration can be achieved by electret substrate. Electrostatic or electret substrate can be a high-loft triboelectric filter medium made by combing and acupuncture. In one of the embodiments, preferably nanoparticles are deposited in substrate before acupuncture, and then electrostatic fibers and nanoparticles are acupunctured together.

[0028] In certain embodiments, the polymer sheet further comprises a binder within the polymer layer, binding the nanoparticles to the polymer layer. The binder may comprise a material selected from the group consisting of starch, dextrin, guar gum, PVOH, and synthetic resins.

[0029] In another aspect, the gas filter comprises a filter medium and a substantially rigid support layer bonded to the filter medium. The support layer comprises fibers and a plurality of nanoparticles arranged within the support layer. The nanoparticles can be configured to filter pollutants passing through the support layer. The support layer can comprise at least one extruded polymer film having one or more holes for gas or liquid to flow through.

[0030] In certain embodiments, the polymer film has a first surface and a second surface opposite to the first surface, and at least a portion of the nanoparticles are arranged between the first surface and the second surface. The polymer film may include at least one fold to form wrinkles in the sheet. The hole may include a pore or a perforation. The hole may have a shape such as a hexagon, a circle, a square or a rhombus.

[0031] In one embodiment, the support layer is substantially porous. In an exemplary embodiment, the support layer has a porosity value of at least 0.5 or 50%, preferably at least 0.8 or 80%, and more preferably about 0.86 or 86%.

[0032] In certain embodiments, the gas filter further comprises a plurality of folds extending across the surface of the polymer layer. The polymer film may be selected from the group consisting of polypropylene film, high density polyethylene film and polylactic acid film. The gas filter may also comprise a net, mesh, fabric, knitted fabric or braid.

[0033] In certain embodiments, the nanoparticles are isolated in the fluid and dispersed by the first surface of the polymer layer. The support layer may include fibers with static charge. The nanoparticles are selected from the group consisting of carbon fiber, glass fiber, polypropylene fiber, nylon fiber, polylactic acid fiber and combinations thereof.

[0034] In certain embodiments, the gas filter further comprises a binder within the polymer layer to bind the nanoparticles to the polymer layer. The binder may comprise a material selected from the group consisting of starch, dextrin, guar gum, PVOH, and synthetic resins.

[0035] In another aspect, a composite material comprises a substrate having pores within an internal structure and a plurality of nanoparticles within the internal structure of the substrate. The nanoparticles form a gradient within the substrate such that a density of the nanoparticles decreases from a first surface to an opposing second surface of the substrate.

[0036] The substrate may comprise a fibrous material. The fibrous material may be a plurality of microfibers, the size of the microfibers being 1 micron or larger.

[0037] In certain embodiments, the microfibers are formed in a process selected from the group consisting of a spunbond process, a meltblowing process, and an electrospinning process.The nanoparticles may extend a distance of about 1 mm to about 3 mm below the outer surface.

[0038] The recitation herein of desirable objectives met by various embodiments of the specification is not intended to imply or represent that any or all of these objectives are present as essential features (either individually or collectively) in the most general embodiment of the specification or in any of its more specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 A gas filter having first and second support membranes and a filter medium is shown;

[0040] Figure 2A and 2B An apertured membrane used as a support membrane is shown;

[0041] Figures 3A-3E Various embodiments of open-pore films with nanoparticles incorporated into the film are shown;

[0042] Figure 4 A double layer of filter media is shown;

[0043] Figure 5A pleated nonwoven filter media is shown;

[0044] Figure 6 A representative air filter is shown;

[0045] Figure 7 A gas filter is shown;

[0046] Figure 8 A system for producing a nonwoven material within a substrate is schematically shown;

[0047] Fig. 9 A system for converting nanofiber clusters into individual nanoparticles is schematically shown;

[0048] Figures 10A-10C Photos of large nanofiber clusters, small nanofiber clusters, and single nanoparticles

[0049] Fig.11 Shows Fig.13 The system's injectors;

[0050] Fig.12 Shows Fig.13 A reactor of the system;

[0051] Fig.13 Another embodiment of a system for converting nanofiber clusters into individual nanoparticles is shown;

[0052] Fig.14 A system for producing a double-layer nonwoven material is shown;

[0053] Fig.15 is a side view of a nonwoven material having nanoparticles dispersed throughout a portion of the material;

[0054] Fig.16 is a side view of a nonwoven material having nanoparticles dispersed throughout the material;

[0055] Fig.17 is a side view of a nonwoven material having nanoparticles dispersed within the material in a gradient manner;

[0056] Fig.18 A nonwoven material having nanoparticles dispersed within the material at a certain depth is shown;

[0057] Fig.19 A nonwoven material having nanoparticles dispersed within the material at a depth and a scrim layer covering the nanoparticles is shown;

[0058] Fig. 20 A double layer nonwoven material having nanoparticles dispersed on the inner surfaces of both layers is shown; and

[0059] Fig.21 An alternative embodiment of a system for producing a nonwoven material in a fluid stream is shown;

[0060] Fig.22A is a photograph of a nonwoven material without the use of an adhesive;

[0061] Fig. 22B is a photograph of a nonwoven material having an adhesive;

[0062] Fig.23A is a photograph of a nonwoven material having nanoparticles dispersed throughout the material in the form of clumps or clusters;

[0063] Fig. 23B is a photograph of a nonwoven material having nanoparticles substantially uniformly dispersed throughout the material;

[0064] Figures 24A-24C Biocomponent fibers incorporated into nonwoven materials are shown; DETAILED DESCRIPTION

[0065] This specification and the accompanying drawings illustrate exemplary embodiments, and should not be considered as limiting, and the claims define the scope of this specification, including equivalents. Without departing from the scope of this specification and the claims, various mechanical, composition, structural and operational changes can be made, including equivalents. In some cases, well-known structures and technologies have not yet been shown or described in detail, so as not to make the description unclear. The same numbers in two or more figures represent the same or similar elements. In addition, as long as feasible, the elements and related aspects described in detail with reference to an embodiment can be included in other embodiments that are not specifically shown or described. For example, if an element is described in detail with reference to an embodiment, and it is not described with reference to a second embodiment, the element can still be claimed to be included in the second embodiment. In addition, the description herein is for illustrative purposes only and does not necessarily reflect the actual shape, size or size of the system or the components shown.

[0066] It should be noted that, as used in this specification and the appended claims, the singular forms "a," "an," and "the," as well as any word used in the singular, include plural referents unless clearly and unambiguously limited to one referent. As used herein, the term "include" and its grammatical variations are intended to be non-limiting, such that recitation of items in a list does not exclude other like items that can be substituted or added to the listed items.

[0067] Unless otherwise indicated, any quantitative values ​​are approximate, whether or not stated with the word "about" or "approximately." The materials, methods, and examples described herein are illustrative only and not intended to be limiting.

[0068] Provided are open-cell polymer layers, sheets, webs or films comprising one or more holes, pores or perforations and incorporating nanoparticles within the polymer layer. The open-cell films can be configured for use in many applications, including finger bandages, surgical gowns, surgical drapes, masks, teeth whitening patches, hydrogel scrims, nasal support materials, electrode support products, filters, food processing, packaging and textile applications, agricultural products, food packaging (e.g., cheese production nets), etc.

[0069] In certain embodiments, the open-pore sheet comprises a supported membrane in a gas or liquid filter. The nanoparticles reduce the overall pressure drop across the supported membrane to increase the efficiency of such filters.

[0070] As used herein, the term "nanoparticle" means any particle having a size less than 1 micron in at least one axis or dimension. For example, a fiber having a diameter or width less than 1 micron and a length greater than 1 micron is a nanoparticle as used herein.

[0071] In certain embodiments, each individual nanoparticle can be a small particle, and its size range is between about 1 to about 1000 nanometers, preferably between about 1 to about 650 nanometers. In the number size distribution, the particle size of at least half of the particles can be measured as 100 nanometers or below. Most of nanoparticles are usually only composed of hundreds of atoms. As the size of nanoparticles approaches the atomic scale, material properties change. This is due to the increase in surface area and volume ratio, causing the surface atoms of the material to dominate the material properties. Due to the very small size of nanoparticles, compared with bulk materials (such as powders, plates, sheets or larger fibers), the surface area of ​​nanoparticles is very large compared to the volume ratio. This feature makes nanoparticles have undesirable optical, physical and chemical properties, because they are small enough to limit their electronics and produce quantum effects.

[0072] In some embodiments, the nanoparticles comprise nanofibers having at least one dimension (i.e., diameter, width, height, etc., depending on the cross-sectional shape of the fiber) less than 1 micron. The nanofibers may have a continuous length, or the nanofibers may have discrete lengths, such as 1 to 100,000 microns, preferably between about 100 and 10,000 microns.

[0073] The substrate discussed herein can comprise the structure of single fiber or line interwoven, interlocked or bonded together.Nonwoven fabrics can include sheet or web structures bonded together by mechanical, thermal or chemical entanglement of fibers or filaments (and by perforated film).They can be substantially flat porous sheets, which are directly made of independent fibers or molten plastics or plastic films.The example of suitable nonwoven material includes but is not limited to the fiber, layer or web of meltblowing, spunbond or spunlace, thermal bonding, bonding combing, air-laid, wet-laid, co-molding, acupuncture, stitching, hydraulic entanglement, etc.

[0074] In certain embodiments, substrate can comprise knitting and / or woven material. Knitted material can comprise any knitting pattern suitable for desired application. Knitted material suitable for filter application comprises weft knitting, warp knitting, knitted mesh, compressed knitted mesh etc. Woven material suitable for filter application comprises textile filter media, such as monofilament fabric, multifilament fabric, nylon net, polyester net, polypropylene net etc. Woven textile can be used for such as mesh filter press filter cloth, woven filter pad and other die-cutting parts, centrifuge filter bag, liquid filter bag, dust collector filter bag, bed dryer filter bag, rotary drum filter, filter belt, leaf filter, roll medium etc.

[0075] In some embodiments, the substrate may include a structure comprising mixed or entangled chopped fibers and / or filaments. As used herein, chopped fibers refer to fibers of limited length. As used herein, filaments refer to fibers with substantially continuous length. In some embodiments, the substrate may include chopped coarse fibers, microfibers, and / or fine fibers. As used herein, "fine fibers" refer to fibers with a diameter less than 1 micron, "coarse fibers" refer to fibers with a diameter greater than 10 microns, and microfibers are synthetic fibers with a diameter less than 10 microns.

[0076] In certain embodiments, the nanoparticles are dispersed in the substrate "at a certain depth". As used herein, the term "at a certain depth" means that the nanoparticles are dispersed across the first surface of the substrate so that at least some of the nanoparticles are disposed between the first and second opposing surfaces in the internal structure of the substrate or medium. In certain embodiments, the nanoparticles are substantially dispersed throughout the entire medium from the first surface to the opposing second surface. In other embodiments, the nanoparticles are in a portion of the medium from the first surface to a position between the first and second surfaces.

[0077] In some embodiments, the nanoparticles are three-dimensionally distributed in space relative to the supporting substrate, which can increase the fiber surface area and micro volume within the nonwoven material. The three-dimensional distribution can also prevent complete clogging of a specific portion of the nonwoven material, which is particularly useful in filter media because it allows fluids (e.g., air and other gases) to pass through the filter, thereby reducing the overall pressure drop on the filter.

[0078] In other embodiments, the nanoparticles are arranged with a density gradient across the thickness of the substrate, so that the density of the nanoparticles arranged near a surface is higher than the relative surface, or compared with the middle part of the substrate, the density of the nanoparticles arranged on the surface is higher. The density gradient can be substantially linear, it can be reduced in the form of a series of discrete steps, or the gradient can be random (that is, the reduction of density is usually not linear or step-wise). This density gradient provides many advantageous features (as described below) for some applications (such as filters).

[0079] Nanoparticles can include any suitable material, such as glass, biosoluble glass, ceramic materials, acrylic, carbon, metals (e.g., alumina), polymers (e.g., nylon, polyethylene terephthalate, etc.), polyvinyl chloride (PVC), polyolefins, polyacetals, polyesters, cellulose ethers, polyalkylene sulfides, poly(arylene oxides), polysulfones, modified polysulfone polymers and polyvinyl alcohol, polyamides, polystyrene, polyacrylonitrile, polyvinylidene chloride, polymethyl methacrylate, polyvinylidene fluoride, and any combination thereof.

[0080] In some embodiments, the nanoparticles can be made into bicomponent segmented cakes and islands. Then, the filaments are stretched to obtain submicron filaments. The continuous filament nanofibers are cut according to the desired length (preferably about 100 to about 10,000 microns).

[0081] In some embodiments, nanoparticles are absorbents and adsorbents. In some embodiments, nanoparticles are activated carbon fibers or activated carbon powder. In some embodiments, nanoparticles are catalytic particles or catalytic fibers. In some embodiments, nanoparticles can be obtained by feeding submicron fiber nonwovens to pulverizer or crusher or trimmer, wherein the bonded nonwoven enters, and obtains short-cut fibers. For example, low weight biocomponent melt-blown or nano melt-blown fabrics can be fed to pulverizer, and submicron nanoparticles can be obtained.

[0082] In some embodiments, different nanoparticles can be mixed. For example, nanofibers and nanobeads can be mixed. Two different nanofibers with different melting points can also be mixed so that the nanoparticles with a lower melting point can serve as a binder for the nanofibers with a higher melting point. Nanoparticles with different diameters and different lengths can also be mixed.

[0083] In some embodiments, the nanoparticles are selected from environmentally sustainable raw materials. The nanoparticles can be biosoluble glass nanofibers, biodegradable nanoparticles, compostable nanoparticles, or recyclable compositions.

[0084] Different types of nanoparticles can be combined. Some nanoparticles can be functional nanoparticles. For example, functional nanoparticles can include activated carbon and / or antibacterial materials deposited on and / or attached to fibers in a nonwoven material. This can improve the gas absorption efficiency of the fiber and the effectiveness of killing bacteria. In addition, a composite product of an open-pored sheet with glass and carbon nanoparticles deposited thereon will provide filtering and deodorizing functions as a filter medium.

[0085] In some embodiments, nanoparticles are attached to substrates by mechanical entanglement. This mechanical bonding can be supplemented with adhesives and / or tackiness agents, as discussed in more detail below. In certain embodiments, nanoparticles are not curled (i.e., they do not include the obvious wavy, curved, curled, coiled sawtooth or similar shapes associated with the nanoparticles in a relaxed state). In other embodiments, nanoparticles can have a curled body structure with discrete lengths. For example, when these curled nanofibers with discrete lengths are attached to substrates, they entangle with each other, and also attach to substrates, attach to substrates and attach to substrates around. In other embodiments, the attachment of nanofibers to substrates is achieved by attracting electrostatic charge and / or van der Waals forces between substrates and nanoparticles.

[0086] Also provided are filter media and filters, such as air filters, masks, gas turbine and compressor intake filters, plate filters, etc., which include nanoparticles dispersed in the filter media at a certain depth. In some embodiments, the filter includes one or more support layers bonded to the filter media. The support layer and / or the filter media can include nanoparticles dispersed in the layer at a certain depth. In some embodiments, a polymer layer, a membrane layer or a membrane is provided, which includes one or more holes for gas or liquid to flow through, and the nanoparticles are arranged in the polymer layer at a certain depth. In other embodiments, the substrate comprises a nonwoven material that forms a flexible surface layer for finger bandage pads, masks, etc.

[0087] Provided herein are systems, devices and methods for producing composite materials and products containing composite materials (e.g., gas filters). Also provided are systems and methods for isolating single nanoparticles in a gaseous medium (e.g., air, helium, nitrogen, oxygen, carbon dioxide, etc.) (rather than a liquid), and the single nanoparticles can be dispersed into another product, film, layer or substrate by airflow, aerosol, evaporator, spray or other suitable delivery mechanisms.

[0088] Although the following description is mainly directed to composite materials and filter media, it should be understood that the devices and methods disclosed herein can be easily adapted to various other applications. For example, the composite materials disclosed herein can be used in household cleaning products, roofing and flooring products, automotive interiors and headliners, reusable bags, wall coverings, filtration devices, insulation materials, etc. In addition, the isolated and generated single nanoparticles can be used in various coatings, composite materials and / or additives, for example, polymers, food packaging, flame retardants, fuel cells, batteries, capacitors, nanoceramics, lamps, material manufacturing, production methods, reinforcements for composite materials, cements and other materials, medical diagnostic applications, medical treatment devices or therapies, tissue engineering (e.g., scaffolds for bone or tissue repair), drinking water, industrial process fluids, food and beverage products, drugs and biologics, tissue imaging, medical treatment delivery, environmental applications (e.g., biodegradable compounds), etc.

[0089] refer to Figure 1 , the composite filter member 114 includes an internal filter substrate 112 and one or more filter support members or membrane layers 110. The support member 110 can be formed by an extruded sheet of a polymer, such as a polypropylene film, a high-density polyethylene film, a polylactic acid film, or a thermoplastic polymer material, such as an extrudable fluoroplastic material, in an embodiment, a perfluoroalkoxyalkane (PFA) copolymer made from comonomers polytetrafluoroethylene and perfluoroalkyl vinyl ether. However, other polymer materials can be used, such as fluoroplastics, such as ethylene chlorotrifluoroethylene (ECTFE), ethylene tetrafluoroethylene (ETFE), or polyvinylidene fluoride (PVDF).

[0090] In certain embodiments, the support membrane layer 110 comprises individual nanoparticles dispersed at a depth within the membrane layer 110. The nanoparticles allow the support membrane layer to filter at least some contaminants that pass through the filter membrane layer 114, i.e., in addition to the filtration provided by the internal filter substrate 112. In other embodiments, the filter substrate 112 and / or the support membrane layer 110 include such nanoparticles.

[0091] Fluoroplastic materials such as PFA are well suited for use in filters for cleaning semiconductor components and other environments where extremely high cleanliness is required and the potential for contamination is minimized. Such support membrane layers are designed to direct fluids along their surfaces and also to direct fluids through the structure into the underlying filter substrate to remove unwanted particles from the filtrate.

[0092] like Figure 2A and 2BAs shown, the support film layer 110 may include a plurality of holes 128. The shape of the holes is preferably circular, but it will be appreciated that other shapes are also possible, such as square, rectangular, hexagonal, triangular, etc. The substrate may be wound into a roll, then unwound and directed through a punching machine to form the desired predetermined pattern of holes 128 in the Z direction ( Figure 2A ). Optionally, after being disposed, the sheet may be directed through a punch press in a continuous operation to form a predetermined pattern of holes 128 therein.

[0093] refer to Figure 2B After opening the apertures, the filter support member can be stretched in the machine direction, as shown by double-headed arrow 141, to elongate the apertures 128 for providing a larger open area for the fluid to be filtered by the filter medium or substrate 112. The apertured substrate can be made using any suitable method known in the art. A more complete description of such a composite filter medium can be found in PCT Application Serial No. US2021 / 011217, the complete disclosure of which is hereby incorporated by reference in its entirety for all purposes.

[0094] In an alternative embodiment, the support membrane 110 layer can be porous (i.e., not having pores 128, or in addition to having pores 828). In this embodiment, additional fluid flow can be achieved through the substantially porous support membrane layer. In an exemplary embodiment, the porosity value of the support membrane layer is at least 0.5 or 50%, preferably at least 0.8 or 80%, and more preferably about 0.86 or 86%. The porosity value is defined as the non-solid or pore volume fraction of the total volume of the material.

[0095] The support membrane layer of the present filter can be prepared by any method known to those skilled in the art. Figure 2A and 2B In one example shown, the support film layer includes ribs. For example, the support film layer can be made by extruding a polymer material to form a sheet and then passing the sheet through a nip area provided by opposing rollers; at least one roller has an outer surface with countersunk grooves. The countersunk grooves in one roller are aligned with the outer surface or the countersunk grooves of the other roller in the nip area to form a ribbed sheet having ribs upstanding from at least one surface of the sheet. Optionally, the ribs can be formed in an extrusion process or a known embossing method. Once the ribs are formed, the support film layer can be wound into a roll, subsequently unwound and guided through a press to form a desired predetermined pattern of holes in the Z direction thereof. Optionally, after setting, the support film layer can be guided through a punch press in a continuous operation to form a predetermined pattern of holes therein, such as Figure 2A Optionally, the support film layer can be stretched in the machine direction ( Figure 2BThe pores may be elongated to provide a larger open area for a fluid to be filtered through, for example, a filter layer or substrate.

[0096] Figures 3A to 3E Several examples of open-cell membranes that can be used as composite substrates are shown. The holes can be provided in various patterns having one or more shapes. Various types of sheets can be combined, and one or more layers can be used. Sheets of different materials can be combined. Open-cell polymer sheets can provide support for the filter medium, for example, or separate layers can be attached to provide the desired structural support. In certain embodiments, the substrate can be included in a film or layer that includes holes, pores, or perforations. The holes can be embossed into a pattern (e.g., circles, diamonds, hexagons, rectangles, triangles, rectangles, etc.) and then stretched until holes are formed in the thinned areas produced by the embossing. Such open-cell substrates can be formed from a variety of polymers (e.g., polypropylene, polyethylene, high-density polyethylene ("HDPE"), etc.). The polymer layer can, for example, comprise an extruded film. Open-cell membranes are commercially available and are available as The substrate is provided in the form of a roll and the nanofibers are deposited into the substrate in a roll-to-roll process. Figures 3A-3E Examples of apertured films formed using the methods described herein are shown.

[0097] In certain embodiments, composite material is formed by perforated sheet substrate, and nanoparticles are deposited in perforated sheet.Substrate has a first surface and a second surface relative to the first surface, and defines width or thickness between the first and second surfaces.In certain embodiments, nanoparticles have been deposited into substrate by the first surface.Nanoparticles penetrate into a substrate of a certain "depth" between the first and second surfaces by the first surface.In some embodiments, nanoparticles penetrate at least 25% of the width or thickness between the first and second surfaces from the first surface, or more preferably penetrate at least about 50% of the thickness.In other embodiments, nanoparticles are substantially permeated throughout the substrate from the first surface to the second surface.

[0098] The nanoparticles preferably include individual nanoparticles (e.g., Fig. 23B As shown in Figure 2 ), the nanoparticles are not present in the composite product in the form of layers, and there are no obvious nanofiber agglomerates or bundles (as shown in Figure 2 ). Fig.23A This allows the nanoparticles to be more dispersed throughout the substrate, which in some applications (e.g., gas filters) provides a more effective filtration capability to filter out pollutants. In addition, this provides a composite material with a greater area density (in grams per square meter (gsm)) or "addition amount" of nanoparticles within the material. The term "addition amount" as used herein means the area density (gsm) of a material, fiber or particle in a thin layer, sheet or film of a material.

[0099] In certain embodiments, the nanoparticles may comprise about 0.1 g / m 2 About 20 g / m 2 , preferably at least about 2.0 g / m 2 The specific amount of addition or surface density may depend on the application. For example, the applicant has found that a higher surface density or addition will increase the efficiency of the nonwoven material in filtering pollutants. Therefore, the specific amount of nanoparticles added may depend on the desired efficiency of the filter medium.

[0100] In certain embodiments, composite material comprises substrate and the nanoparticles of the whole width of infiltration throughout substrate.In certain embodiments, nanoparticles are basically dispersed throughout substrate.In certain embodiments, the density of the nanoparticles positioned at the first surface is less than 50% with the difference of the density of the nanoparticles dispersed in the central part of substrate.In some embodiments, this difference is less than 25%, preferably less than 10%.In certain embodiments, the amount or quantity of the single nanoparticles dispersed in the central part of substrate is at least about 50% of the amount of the single nanoparticles dispersed in or near the first surface, preferably at least about 75%, and more preferably at least about 90%.In other embodiments, nanoparticles 14 are arranged with density gradient from the first surface to the second surface.

[0101] Contemplated nanoparticles may be produced by any method including, but not limited to, air laying, spinneret, gel spinning, melt spinning, wet spinning, dry spinning, island-in-the-sea staple fibers or spunbond, segmented cake staple fibers or spunbond, etc. Such methods have been described in U.S. Pat. Nos. 4,406,950, 6,338,814, 6,616,435, 6,861,142, 7,252,493, 7,300,272, 7,309,430, 7,422,071, 7,431,869, 7,504,348, 7,774,077 9,522,357, 9,993,761 and U.S. Patent Publication Nos. 2009 / 266,759, the entire disclosures of which are hereby incorporated by reference herein for all purposes.

[0102] Figure 4A double-layer filter medium is shown, which includes a first substrate 240 having a first surface 242 and a second surface 244 opposite to the first surface. The second substrate 250 has a first surface 252 and a second surface 254 opposite to the first surface. The second surface 244 of the substrate 240 is bonded to the second surface 254 of the first substrate in any manner known to those skilled in the art. The substrate may include a polymer sheet, a nonwoven material, a knitted fabric, a braided fabric, a mesh, etc. For example, the first substrate 240 may include an open-cell polymer sheet, and the second substrate 250 may include a nonwoven material of microfibers. In another example, the first substrate 240 contains fibers 246 with a relatively small linear density (e.g., about 3 deniers or less), and the second substrate 250 contains fibers 256 with a relatively large linear density (e.g., about 3 deniers or greater, such as 5 deniers, 6 deniers or greater). One or both substrates include individual nanoparticles (not shown) dispersed throughout the substrate and bonded to the substrate and / or retained by the substrate. A two-layer composite material in certain embodiments may be formed using a polymer sheet as described above, attached to a composite material formed from a nonwoven substrate, wherein one or both substrates have nanoparticles attached to and deposited to a depth in the substrate.

[0103] The first substrate 240 is configured to filter contaminants primarily using fibers 46, but as previously described, the first substrate 240 may also include nanoparticles. The second substrate 250 is configured to filter contaminants using fibers 256 and nanoparticles.

[0104] In some embodiments, the substrate may contain additives, such as antimicrobial and / or antiviral compositions, such as silver, zinc, copper, silicone, tributyltin, organic compounds containing chlorine, bromine or fluorine compounds.

[0105] In certain embodiments, composite materials (i.e., substrates and / or nanoparticles) can be electrostatically charged, so that, for example, pollutants can be captured by mechanical and electrostatic filtration. The bonding between substrate and nanoparticles can also be enhanced by electrostatically charging nanoparticles, substrates, or both. For example, in certain embodiments, substrates are electrostatically charged, so that mechanical filtration can be achieved by nanoparticles, and electrostatic filtration can be achieved by electret substrates.

[0106] The substrate, nanoparticles, or both may be electrostatically charged using triboelectric methods, corona discharge, electrostatic fiber spinning, hydrocharging, charging rods, or other known methods. Corona charging is applicable to charging single polymer fibers or fiber blends or fabrics. Tribocharging may be applicable to charging fibers with different electronegativity. Electrostatic fiber spinning combines the charging of polymers and the spinning of fibers into a one-step process. Methods suitable for triboelectric charging are described in U.S. Pat. No. 9,074,301, the entire disclosure of which is hereby incorporated by reference herein for all purposes.

[0107] Nanoparticles can be selected to have different triboelectric properties relative to the substrate to enhance particle removal using the triboelectric effect. With this approach, the resulting nanoparticles are formed in an electric field and are less susceptible to contamination by chemicals that can mitigate the triboelectric effect.

[0108] Composite materials can include adhesives or bonding materials, such as glues or adhesives, to promote the attachment of nanoparticles and / or the retention of nanoparticles in substrates, so that nanoparticles can adhere to the substrate, or otherwise be retained by the substrate, be retained in the substrate, to form a stable base. Adhesives or bonding materials are preferably present in relatively small amounts to bond individual nanoparticles to the substrate.

[0109] The adhesive may comprise a variety of conventional materials, including natural based materials such as starch, dextrin, guar gum, etc., or synthetic resins such as EVA, PVA, PVOH, SBR, polyglycolide, etc. In certain embodiments, a solvent based adhesive is used, wherein bonding occurs upon evaporation of the solvent.

[0110] In a preferred embodiment, the adhesive or adhesive material comprises dextrin. In yet another embodiment, the adhesive comprises a composition of various substances (e.g., water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzene sulfonate, lauramine oxide, and ammonium hydroxide). In yet another embodiment, the adhesive comprises at least PVOH. The adhesive can be a solution, emulsion, suspension, hot melt, curable, pure, and / or a combination.

[0111] In some embodiments, adhesive resin is used, and adhesive resin can be cross-linked after adhesive is applied to substrate. Adhesion (water resistance / solvent resistance) can be promoted by self-crosslinking when solvent evaporates in adhesive formulation or heat activation in drying process. For some adhesives, crosslinking can be achieved by electromagnetic radiation (including but not limited to RF, UV or electron beam) of high energy wavelength. The amount of adhesive can be controlled by adjusting the nozzle size of sprayer 140 or the flow rate of control adhesive composition. Adhesive can be applied using nozzle, dip coating or other methods.

[0112] In some embodiments, the adhesive or adhesive material may include a surfactant to reduce the surface or interfacial tension of the adhesive, thereby increasing its dispersibility and wettability, and making it easier for the adhesive to penetrate into a substrate at a certain depth. Suitable surfactants for use with the adhesive disclosed herein include nonionic surfactants, anionic surfactants, cationic surfactants, and amphoteric surfactants, such as sodium stearate, 4-(5-dodecyl)benzenesulfonate, sodium dodecylbenzenesulfonate wetting agents, docusate (dioctyl sodium sulfosuccinate), alkyl ether phosphates, benzalkonium chloride (BAC), perfluorooctane sulfonate (PFOS), etc.

[0113] In some embodiments, the substrate comprises its own adhesive composition. In these embodiments, an adhesive or bonding material may or may not be added to the substrate. In one such embodiment, the substrate comprises biocomponent fibers, wherein one of the component species comprises an outer sheath at least partially surrounding the kernel, as discussed further below.

[0114] Fig.22A is a magnified image of a composite product in which nanoparticles are deposited without using a binder material. Fig. 22B is an enlarged image of a composite product in which a binder material of dextrin and water is used to adhere the nanoparticles to the fibers. As shown, with the use of a binder, the nanoparticles are more uniformly adhered to the substrate.

[0115] Fig.22A A substrate is shown having biosoluble glass nanofibers deposited in a layer only on the substrate surface, relying on electrostatic forces to retain the nanofibers. Fig.22A Agglomeration of nanofibers can be seen in the nanofibers, and the retention rate of nanofibers is very poor. The substrate can be a polymer sheet, a knitted fabric, a braided fabric, a net or a nonwoven material. In a further embodiment, the composite material with one or more polymer sheets as the substrate can include a binder material for retaining nanoparticles using the above materials.

[0116] In a further example, any adhesive material disclosed herein can be used. In addition, the nanoparticles of biosoluble glass have been deposited into a substrate at a certain depth. In this example, the substrate itself has a MERV rating of 4 to 10, which can be achieved using any method described herein. In one example, due to the deposition of nanoparticles into a substrate at a certain depth and with static charge, a substrate having a MERV of 8 initially has been used to produce a composite product having a MERV of 13. In another example, a substrate having a MERV of 6 initially has been used to produce a composite product having a MERV of 15. The substrate is provided on a roll, and in a roll-to-roll continuous process, the composite product can be produced on a commercial scale, as any process and method described herein. In an example, the roll-to-roll process runs at a speed of 30 feet per minute.

[0117] In certain embodiments, the composite materials discussed herein can be used as part of a filtration device that captures or absorbs pollutants, such as a liquid filter, a gas filter for home and commercial air filtration, a surgical mask or other face mask, etc. The filtration device can be a mechanical filter, an absorption filter, a barrier filter, an ion exchange filter, a reverse osmosis filter, a surface filter, a depth filter, etc., and can be designed to remove many different types of pollutants from air, water, or other media.

[0118] In one such embodiment, the composite material is incorporated into an air filter that removes particles and pollutants from the air, such as a HEPA filter (i.e., a pleated mechanical air filter), a UV line filter, an electrostatic filter, a washable filter, a media filter, a glass fiber filter, a pleated or non-pleated air filter, an activated carbon filter, a bag filter, a V-bank compact filter, a filter sheet, a flat cell filter, a filter cartridge, etc. The composite material can include a filter medium for an air filter, and can be supported by a support layer, a scrim layer, or can be included in other layers or materials. Applicants have found that, as discussed herein, incorporating nanoparticles into the composite material at a certain depth significantly improves the efficiency of the air filter without compromising other factors, such as the pressure drop (i.e., air flow) through the filter. In addition, these materials increase the overall dust holding capacity, thereby extending the life of the filter, particularly compared to filters that only or primarily rely on electrostatic effects to improve efficiency.

[0119] Traditional home and commercial air filters are typically rated based on the filter's ability to capture particles ranging from approximately 0.3 to 10 microns. This rating is called the Minimum Efficiency Reporting Value, or MERV, and is established by the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE). MERV ratings range from 1-16, with higher values ​​indicating greater efficiency in capturing a particular type of particle. Traditional mechanical air filters typically report a MERV rating of about 8 for the filter material.

[0120] Air filters are usually rated based on their initial efficiency (i.e., the efficiency of the air filter before use) and their efficiency over time and use. The latter efficiency is usually tested through a conditioning procedure, known as Annex J of ASHRAE Standard 52.2.

[0121] The air filters provided herein have an initial MERV rating greater than about 10 and a pressure drop of less than about 0.5 inches of water column. In some cases, the initial MERV rating is about 11 and the pressure drop is equal to or less than about 0.17 inches of water column, or the initial MERV rating is about 13 and the pressure drop is equal to or less than about 0.36 inches of water column, or the initial MERV rating is about 14 and the pressure drop is equal to or less than about 0.5 inches of water column.

[0122] The gas filters provided herein have a MERV rating of 10 or higher after conditioning according to ASHRAE Standard 52.2, Appendix J. In some embodiments, the MERV rating is 13 or higher after conditioning according to ASHRAE Standard 52.2, ISO Standard 16890, or any other acceptable standard in the industry.

[0123] The MERV ratings of the filter media discussed herein will vary based on many factors, including the type and size of fibers used in the filter media, the density of individual nanoparticles within the filter media, the width of the filter media, the number and size of pleats (if any), etc. MERV ratings can be measured for sheets of composite products as well as composite products formed into pleated filter media, and the pressure drop for each product can be different. Likewise, the pressure drop across the filter media will also depend on many factors, including those described above.

[0124] One factor that affects the MERV rating and pressure drop is the density or amount of nanoparticles added within the substrate relative to the density of fibers within the substrate. In certain embodiments, the nanoparticle surface density of the filter media described herein is about 0.1 g / m 2 About 20 g / m 2 , preferably at least about 2 g / m 2 .

[0125] The efficiency or MERV rating of the filter can be increased as the amount of nanoparticles added increases. In particular, the applicant has found that, for example, an addition amount of at least 2 g / m 2 A filter with a MERV rating of approximately 10 can be achieved. 4 or 6 g / m 2 The addition of 10 g / m 2 Addition levels of 1% or more produce filters with a MERV rating of 15 or higher.

[0126] Figure 5 An example of a pleated filter media 390 is shown in FIG. Depending on the application, the filter 390 may include about 0 to 10 pleats per inch. The filter media may be mounted in a cardboard or metal frame and used as an easily replaceable filter product ( Figure 6 As shown, a gas filter 394 produced using the composite material described herein includes a pleated filter media 396 and a support layer 398 that provides rigidity and structure to the filter media 396.

[0127] Figure 7A gas filter 309 produced using the composite material described herein is shown. The gas filter 309 includes a substrate and nanoparticles dispersed in the substrate at a certain depth. The substrate is then rolled into a cylinder, cone, or other suitable shape and can be used in applications such as gas turbine and compressor intake filters, panel filters, etc.

[0128] Other types of filters that can be developed using the composite materials disclosed herein include conical filter cartridges, square end cap filter cartridges, bag filters, V-bank compact filters, plate filters, flat cell filters, pleated or non-pleated bag filter cartridges, and the like.

[0129] The composite product disclosed herein can be used for medical masks or other medical applications, such as filter cartridges in respirators. Medical masks are intended to protect medical staff and / or patients from microorganisms and other substances. For example, medical masks can block bacteria (e.g., their size can be about 3 microns) and viruses (e.g., their size can be about 0.1 microns). The mask is made of a multi-layer composite material and has ear loops, laces or other structures for attaching the mask to the face of a person. Some layers may include composite materials with non-woven substrates, polymer sheets or layers, etc. Metal wire can be incorporated into at least the upper portion of the mask so that at least this portion fits the face of a person. The mask may include a rigid polymer structure for fixing the multi-layer composite material in front of the face of a person. In one example, the mask has three layers. The outer and inner layers contain non-woven materials (e.g., spunbonded polypropylene) that provide breathability, but any material mentioned herein may also be used. The middle layer is located between the inner layer and the outer layer and comprises a polymer open-cell sheet substrate having nanoparticles deposited into the substrate to a depth to provide an initial MERV greater than 8, preferably greater than 10 MERV, and more preferably 13 or greater MERV. The pressure drop through the mask is 3 to 6 mm water column, and for breathability, 4 mm water column is more preferred. The efficiency of the mask is expected to be about 95%. Other examples of masks have four or more layers. Multi-layer composite products can be combined into a single mask.

[0130] Figure 8 The overall system 410 for producing the above-mentioned composite materials and other products is schematically depicted. As shown, the system 410 includes a feeder 420 for advancing a substrate 430, such as a polymer sheet or other material, during the production process. The system 400 further includes a coater 440, a fiberizing system 450, and a heating and / or drying device 460. In certain embodiments, the system 400 also includes a vacuum or other negative pressure source 470 located below the substrate 430, which is opposite to the fiberizing system 450.

[0131] In one embodiment, feeder 420 includes a winder 424 at the downstream end of the process and an unwinder 422 at the upstream end, which continuously winds a substrate 430 passing through system 400. In certain embodiments, feeder 420 may also include a support surface (not shown) extending between the winders for supporting substrate 430 as it moves downstream through system 400. In other embodiments, the substrate is unwound directly from unwinder 422 to winder 424 without another support surface.

[0132] The coater 440 is configured to spray droplets of an adhesive or bonding material (e.g., an adhesive or other adhesive) onto the substrate 430 so that the nanoparticles can adhere to the substrate 430 to form a stable base. The adhesive is preferably present in a relatively small amount to bond individual nanoparticles to the fibers throughout the substrate 430. In a preferred embodiment, the coater 440 includes a nozzle sized to generate adhesive droplets having a diameter of about 20 to 30 microns to increase the penetration depth of the adhesive through the substrate 430. Of course, the droplet size may be affected by many other parameters, including air pressure, air volume, air temperature, humidity, spray horn design, rheology / viscosity of the adhesive, carrier, etc.

[0133] Of course, it should be recognized that coating the substrate with the adhesive or bonding material can be achieved by other coating methods including ultrasonic spraying, dip coating, spin coating, gravure coating, kiss roll coating, screen coating, powder coating, electrostatic, sputtering or similar coating techniques.

[0134] As described above, the adhesive may include various conventional materials, including natural based materials such as starch, dextrin, guar gum, etc., or synthetic resins such as EVA, PVA, PVOH, SBR, etc. In certain embodiments, a solvent based adhesive is used, wherein bonding occurs when the solvent evaporates.

[0135] In a preferred embodiment, the adhesive comprises dextrin. In another embodiment, the adhesive comprises a composition of various substances (e.g., water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzene sulfonate, lauramine oxide, and ammonium hydroxide). In another embodiment, the adhesive comprises PVOH. The adhesive can be a solution, emulsion, suspension, hot melt, curable, pure, and / or a combination.

[0136] In some embodiments, adhesive resin is used, and the adhesive resin can be cross-linked after the adhesive is applied to the substrate 430. Adhesion (water resistance / solvent resistance) can be promoted by self-crosslinking when the solvent in the adhesive formulation evaporates or thermal activation during drying. For some adhesives, crosslinking can be achieved by electromagnetic radiation of high energy wavelength (including but not limited to RF, UV or electron beam). The amount of adhesive can be controlled by adjusting the nozzle size of the spray coater 440 or controlling the flow rate of the adhesive composition.

[0137] In some embodiments, the adhesive can include a surfactant to reduce the surface or interfacial tension of the adhesive, thereby increasing its dispersibility and wettability, and making it easier for the adhesive to penetrate into a substrate at a certain depth. Suitable surfactants for use with the adhesive disclosed herein include nonionic surfactants, anionic surfactants, cationic surfactants, and amphoteric surfactants, such as sodium stearate, 4-(5-dodecyl)benzenesulfonate, sodium dodecylbenzenesulfonate wetting agents, docusate (dioctyl sodium sulfosuccinate), alkyl ether phosphates, benzalkonium chloride (BAC), perfluorooctane sulfonate (PFOS), etc.

[0138] In some embodiments, spray coater 440 is located upstream of fiberizing system 450 so that the binder is sprayed before the nanoparticles are deposited. In other embodiments, spray coater 440 is located downstream of fiberizing system 450 so that the binder is sprayed after the nanoparticles are deposited. In other embodiments, system 400 includes two spray coaters; one is located upstream of fiberizing system 450, and a second spray coater (not shown) is located downstream of fiberizing system 450 to coat substrate 430 with a second binder after the nanoparticles are deposited.

[0139] In some embodiments, each spray coating machine 440 has more than one nozzle head.For example, nozzle heads can be arranged in series, to obtain better uniformity or increase fiber spraying width.Alternatively, nozzle heads can be placed in parallel (i.e. across the width of substrate) to ensure that adhesive is applied on the whole width of substrate.In some embodiments, substrate includes its own adhesive composition.In these embodiments, adhesive may be added to or may not be added to substrate.The adhesive material mixed in the substrate material may be used in combination with other adhesive materials sprayed on substrate.

[0140] In a preferred embodiment, a negative pressure source or vacuum source is disposed below the substrate, opposite to the spray coater 440, to increase the penetration depth and uniformity of the adhesive. The negative pressure source can be any suitable suction device that draws the adhesive through the substrate, such as a suction pump, etc.

[0141] The substrate can include a material that is bonded to the nanoparticles. For example, the substrate can include a material that becomes sticky and / or flows when heated and / or dried. During the heating / drying step, the substrate is heated to its melting point until it becomes sticky and / or flows so that the nanoparticles are bonded to the substrate. In a preferred embodiment, bonding and drying are carried out simultaneously in drying device 460.

[0142] Fig. 9 Schematically depicted is a fiberizing system 450 for converting clumps or clusters of nanofibers into individual nanoparticles. As used herein, the term "fiberizing" means converting (e.g., opening, separating, isolating and / or singulating) clusters, clumps, or other groups of nanoparticles that may or may not be entangled with each other into individual nanoparticles having at least one dimension less than 1 micron. Figures 10A-10C shows large clusters of entangled nanofibers ( Fig.14 A), small clusters of entangled nanofibers ( Fig. 10B ) and single nanoparticles ( Fig. 10C ) instance.

[0143] As shown, the fiberizing system 450 includes a feeder 500, such as a hopper, for feeding relatively large or large clusters / agglomerates of nanoparticles (see Fig. 10A ) is introduced into the system 450. The feeder 500 may comprise any suitable hopper device known to those skilled in the art, and is preferably configured to introduce large particle clusters into the process at a specified rate, which rate depends on the fiberization rate downstream. The nanoparticles may be introduced continuously at a specified rate, or at intervals of a specific rate. The bundled large clusters of nanoparticles may be broken up before being introduced into the feeder 500.

[0144] It should be appreciated that the nanoparticles can be introduced into the fiberizing device 450 in a variety of different forms. For example, the raw nanofibers can be produced as long separate fibers. In this form, the nanofibers can be cut to obtain the desired aspect ratio.

[0145] The system 450 also includes a separator 510, such as a blender, for separating or decomposing large clusters / agglomerates of nanoparticles into small clusters / agglomerates of nanoparticles (see Fig. 10B ). The feeder 500 delivers the nanofibers to the separator 510 in a stable and continuous state by any mechanical means. The delivery speed will depend on a variety of factors, such as the speed of the substrate 430 along the feeder 420, the fiberization rate of the nanoparticles, etc. By controlling the amount of nanoparticles falling into the separator 510, the amount of nanoparticles dispersed into the substrate can be controlled, thereby achieving a continuous production process.

[0146] In one embodiment, the separator 510 includes a housing 512 having a first opening 514 coupled to the feeder 500 and a second opening 516 coupled to the downstream process. The size of the second opening 516 preferably allows only nanofiber clusters of a certain size to pass through. The separator 510 may include a plurality of rotatable blades (not shown) designed to rotate around a vertical axis within the housing 512 to separate and open the coarse nanofiber clusters. The plurality of blades may have the same or different pitches and cambers to allow the entangled fibers to be sequentially decomposed or "opened" when moving from the first opening 514 to the second opening 516.

[0147] The fiberizing system 450 also includes an airflow (discussed in more detail below) that extends throughout the system from the separator 510 to the nozzle 520. The airflow (along with a series of pumps discussed below) provides the motive force for moving the nanofibers through the system 450. In one embodiment, the airflow is generated by an air compressor 530 configured to supply compressed air to the system, but it will be appreciated that other forms of gas may be used to transport the nanofibers through the system 450.

[0148] The system 450 includes one or more pumps for moving the nanofiber clusters and ultimately individual nanoparticles throughout the system. The pump may include any suitable pump, such as a positive displacement pump, a centrifugal pump, an axial flow pump, etc. In one embodiment, the first pump 540 includes a first inlet fluidically coupled to the air compressor 530 through a first channel 542 and a second inlet fluidically coupled to the separator 510 through a second channel 544. Compressed air is sucked into the first pump 540, which generates a negative pressure (e.g., a vacuum) to draw the nanofiber clusters from the separator 510 into the pump (discussed in more detail below). The system 550 may also include a second pump and a third pump 550, 560, each of which is coupled to the outlet fluid of the first pump 540. Similarly, the second pump and the third pump 550, 560 generate a negative pressure to pull the nanofiber clusters through the third channel 552.

[0149] In certain embodiments, the pump 540 includes an ejector 600. Fig.11 As shown, the ejector 600 each includes a motive fluid inlet 602 and a nanofiber inlet 604, which are coupled to an outlet 606 through a fluid channel 608. The fluid channel 608 includes a converging inlet nozzle 610, a diffuser throat 612, and a diverging outlet diffuser 614. High-pressure, low-speed air is converted into low-pressure, high-speed air, thereby generating the pressure difference required for suction. Based on the Venturi effect and the Bernoulli principle, the primary fluid medium (e.g., compressed air) is used to generate a vacuum to draw the nanofibers into the ejector 600 and discharge them through the outlet 606. The diameter of the ejector 600 depends on the volume flow rate of the compressed air, the suction force requirements, the pressure drop, and the fluid pressure of the compressed air.

[0150] review Fig. 9 , the third channel 552 includes a joint 554 that divides the third channel 552 into two independent channels, each of which leads to the second pump and the third pump 550, 560. The joint 554 preferably includes a surface or wall that is substantially perpendicular to the third channel 552 to form a T-shaped intersection. As the nanofiber clusters move through the third channel 552, they are pushed toward the surface or wall due to the negative pressure applied by the second pump and the third pump 550, 560. The speed of the nanofibers relative to the joint 554 produces a collision with sufficient kinetic energy to cause at least some of the nanofiber clusters to break up into smaller nanofiber clusters and / or break up into individual nanoparticles having at least one size less than 1 micron.

[0151] To generate the kinetic energy required to break up the nanofiber clusters, air is propelled throughout the system 450 at a rate of about 500 feet per minute (fpm) to about 10,000 feet per minute, preferably about 2,000 fpm to about 6,000 fpm. The system 450 includes a sufficient amount of suction pressure, preferably at least about 20 psi. The suction pressure generates a total pressure of at least about 100 psi throughout the system.

[0152] In certain embodiments, the system 450 further includes fourth and fifth fluid channels 562, 564, which couple the outlets of the second and third pumps 550, 560 to the reactor 570. Fig.12 As shown, the reactor 570 includes a top surface 572, a bottom surface 574, and an inner annular chamber 576 extending from the top surface 572 to the bottom surface 574. The reactor 570 also includes a central tube 575 having an open upper inlet 578 and an outlet 580. The reactor 570 may also include one or more upper outlets 582. The reactor 570 may be coupled to an energy source (not shown) that is configured to generate a vortex of vortex gas in the annular chamber 576. The energy source may include any suitable energy source, such as a pump, a compressor, a generator, etc. The vortex gas preferably flows from the bottom to the top of the reactor 570 around the central tube 575 to move the nanofiber clusters and individual nanoparticles upward from the bottom surface 575 to the top surface 572.

[0153] In another embodiment, the generation of vortex does not require a separate energy source. In this embodiment, nanofiber clusters 590 and single nanoparticles 592 enter reactor 570 through bottom inlets 584, 585, 586, 587. Inlets 584, 585, 586, 587 are tilted upward to facilitate the movement of nanofibers and nanoparticles around central tube 575. In a preferred embodiment, at least one or more of inlets 584, 585, 586, 587 are tilted so that nanofibers and nanoparticles are substantially tangential to central tube 575 when entering reactor 570. Once they enter annular chamber 576, the velocity vectors (speed and direction) of the nanofibers and nanoparticles generate vortices within reactor 570, causing them to swirl around central tube 575 upward to the upper portion of chamber 576. The swirling gas preferably flows from the bottom to the top of reactor 570 around central tube 575 to move nanofiber clusters and single nanoparticles upward from bottom surface 575 to top surface 572. The nanofibers 590 and nanoparticles 592 are blown from the bottom of the reactor to the top without any interference. The vortex in the chamber 576 can further break up (eg, open, separate and / or individualize) the nanofiber clusters 290 as they pass through the reactor 570.

[0154] In some embodiments, the reactor 570 may also be coupled to an energy source (not shown) configured to generate a vortex of rotating gas within the annular chamber 576. The energy source may include any suitable energy source, such as a pump, a compressor, a generator, and the like.

[0155] The system 410 may also include another pump or negative pressure source coupled to the upper outlet 582 (e.g., see Fig.13 ). The negative pressure draws the fibers out of the outlet 582, so that the fibers 590 leave the reactor 570. Since the individual nanoparticles 592 are significantly lighter than the tangled nanofibers 590 that are still gathered together, these individual nanoparticles 592 are sucked into the upper inlet 578 of the central tube 575. At the same time, the larger and heavier nanofiber clusters 590 that have not yet been decomposed are drawn out from the upper outlet 584. The upper outlet 584 can be coupled to other pumps (not shown), or to the first pump 540. In this way, the nanofiber clusters 590 are further decomposed through the process again, thereby forming a re-feed system to further decompose the remaining nanofiber clusters.

[0156] The outlet 580 of the central tube 575 is coupled to the nozzle 220 (see Fig. 9). Individual nanoparticles are drawn into nozzle 520 where they are dispersed onto the substrate surface or into the fiber stream (discussed below). Nozzle 520 may comprise any suitable nozzle known to those skilled in the art. In one embodiment, nozzle 520 has multiple outlets whose outer dimensions are tailored to the size (i.e., area) of the substrate passing under nozzle 520. Nozzle 520 will disperse the nanoparticles onto the substrate at a rate driven by the pressure of the entire system.

[0157] In certain embodiments, system 400 includes more than one nozzle coupled to outlet 580 of reactor 570. The nozzles can be arranged on the substrate in any suitable arrangement (eg, side-by-side, in series, in parallel, etc.).

[0158] It will be appreciated that pump 540 or pumps 550, 560 can feed the nanofiber / air mixture stream directly into nozzle 520 (i.e., bypassing reactor 570). In this embodiment, the pressure within the system is designed to generate sufficient kinetic energy to break up or open up substantially all of the nanofibers into individual nanoparticles, thereby eliminating the need for reactor 570 to separate the nanoparticles from larger fiber clusters.

[0159] Reference Fig.13 , another embodiment of a fiberizing system 620 will now be described. As shown, the fiberizing system 620 includes a separator 625 for separating larger or large nanofiber clusters passing through the system 620 into smaller nanofiber clusters. A first ejector 626 is coupled to the outlet of the separator 625 for pulling the nanofibers from the separator 625 into the system 620. An air compressor (not shown) is also coupled to the ejector 626 to provide a motive fluid, as described above.

[0160] Similar to the previous embodiments, the second and third ejectors 630, 640 are coupled to the outlet of the first ejector 626. The nanofibers are drawn from the first ejector 320 and pushed toward the surface of the T-junction 650 to break up at least some of the nanofibers into smaller clusters or individual nanoparticles.

[0161] Each of the second and third ejectors 630, 640 has an outlet coupled to another T-junction 660, 670. As before, the nanofibers are pushed toward the surface of the T-junction 660, 670 to further decompose them. The T-junction 660, 670 are each coupled to two fluid channels entering the bottom 680 of the reactor. Therefore, the bottom 680 of the reactor has four separate inlets 682, 684, 686, 688 for the passage of nanofibers. Each of these inlets is preferably tilted upward and located at opposite corners of the reactor. This allows the nanofibers to enter the vortex of the reactor and then swirl upward to the upper part 690 of the reactor.

[0162] As previously referenced Fig.12 Said, the reactor comprises an annular chamber, wherein the central tube has an open upper end and a lower end coupled to the nozzle. The nanofibers fully decomposed into single nanoparticles flow through the open upper end and enter the central tube for dispersion by the nozzle. The heavier nanoparticle clusters that have not yet decomposed leave the reactor through one of four independent outlets 692, 694, 696, 698. Ejectors 710, 720 provide the power of extracting nanofibers from the reactor 400, as described above. Outlets 792, 794 are coupled to ejectors 710 by T-shaped intersections 712, and outlets 396, 398 are coupled to ejectors 720 by T-shaped intersections 722, respectively. In this case, the nanofibers flow into one channel from two channels when passing through intersections 712, 722.

[0163] The ejectors 710, 720 are coupled to the T-intersections 730, 740, respectively. As previously described, the nanofibers are pushed into the T-intersections 730, 740 to further decompose them into individual nanoparticles. Then, the T-intersections 730, 740 are coupled to the bottom 780 of the reactor 700 (via inlets 732, 734, 742, 744). This allows the nanofibers to return to the reactor 700 for further processing. This process is continued for each nanofiber cluster until it is completely decomposed into nanoparticles and enters the nozzle through the central tube. As a last step, the individualized nanofibers are sprayed from the nozzle air onto any substrate or mixed with any fiber spinning stream. In this process, the suction is up to 20psi and the pressure is up to 100psi.

[0164] In certain embodiments, the fibrosis system may include a separate control system that monitors nanofibers to determine when they are broken down into individual nanoparticles suitable for passing through a nozzle. The control system may, for example, simply monitor the pressure of the entire system to ensure that enough pressure is applied to the nanofibers to break them down into nanoparticles. Alternatively, the control system may include various sensors arranged by the system to detect the characteristics of nanoparticles, such as weight or size. The sensor may be arranged in, for example, the reactor 700 so that the control system may control the various parameters of the reactor 700, such as the negative pressure applied to outlets 692, 694, 696, 698, the speed of the eddy current of the annular chamber, or the pressure applied to the center tube that nanoparticles are sucked into the nozzle.

[0165] Fig.14Another embodiment of a system 750 for producing a multilayer composite material is shown. As shown, the system 750 comprises a first unwinder and a second unwinder 752, 754 and a single winder 756 for winding a first substrate and a second substrate 760, 762 downstream of the system 750. As in the previous embodiment, the system 750 can also include a support surface (not shown) for each substrate 760, 762. The first unwinder and the second unwinder 752, 754 are used to advance the first substrate and the second substrate 760, 762 into the process, wherein they are connected together and then wound on the single winder 756, as described below. The substrate can include a nonwoven material, a net, a knitted fabric, a braid, a polymer sheet, as described above.

[0166] The system 750 includes first and second spray coaters 770, 772, each located downstream of the first and second unwinders 752, 754, for applying adhesive to the first and second substrates 760, 512. The system 700 also includes first and second fiberizing systems / devices 780, 782, which are located downstream of each spray gun 770, 772. As previously discussed, the fiberizing devices 780, 782 generate individual nanoparticles and disperse the nanoparticles onto the substrates 760, 762.

[0167] After the nanoparticles are dispersed into the substrates 760, 762, the two substrates are connected together at the connection point 790 so that they are advanced downstream together. The two substrates can be bonded to each other at this point, or they can simply be placed one on top of the other.

[0168] The system 750 also includes a heater / drying device, such as an IR oven 792, located downstream of the connection point 790 of the two substrates. The heating / drying device heats and dries the two substrates to bond them to each other and to bond the nanoparticles to the fibers within the substrates. The substrates can, for example, be laminated to each other.

[0169] In certain embodiments, nanoparticles are dispersed in substrates 760, 762. In such an embodiment, system 500 is designed so that nanoparticles are dispersed by the first surface of each substrate. Then, substrates can be connected together so that the first surface faces each other. Alternatively, the first surface can be opposite to each other (that is, substrate is connected at the second relative surface of each substrate). In another embodiment again, the first surface of the first substrate is connected to the second surface of the second substrate.

[0170] In further embodiments, other substrates may be used to form the composite material. Fig.15 and 16Another embodiment of a composite material with nanofibers deposited therein is shown, wherein the substrate is a nonwoven material of microfibers. In certain embodiments, the nanoparticles can be substantially distributed across the thickness of the substrate. In other embodiments, the composite material can include nanoparticles having a density gradient across the thickness of the substrate.

[0171] For example, Fig.17 A substrate 830 is shown in which nanoparticles 814 form a density gradient, wherein the density of nanoparticles 814 near a first surface 816 is higher than the density of nanoparticles 814 near a second surface 818. In some embodiments, the difference between the density of nanoparticles located at the first surface 816 and the density of nanoparticles dispersed at the second surface 818 is greater than about 75%. In some embodiments, the difference is greater than 50%. In some embodiments, the difference is greater than 25%. In some embodiments, the amount or number of individual nanoparticles dispersed at or near the second surface 818 is less than about 50%, preferably less than about 25%, and more preferably less than about 10% of the amount of individual nanoparticles dispersed at or near the first surface 816.

[0172] Fig.17 The density gradient shown in can be substantially linear from the first surface 816 to the second surface 818. Alternatively, the density of the nanoparticles 814 can decrease from the first surface 816 to the second surface 818 in a series of discrete steps, or the gradient can be random (i.e., the decrease in density is generally not linear or step-like). The substrate of the composite material can be a polymer open-cell sheet, a woven fabric, a knitted fabric, a mesh, a nonwoven, etc.

[0173] The distribution of nanoparticles across the thickness of the composite material can be measured, for example, using imaging techniques. A magnified view of the composite product taken at a horizontal cross section at the middle of the thickness of the product using electron microscopy or other techniques can be compared to an image taken at the upper or lower surface of the product, or all three images can be compared, to determine the extent of variation in the amount of deposited nanoparticles. Computer image analysis processing can be employed. For example, in Fig.17 In the present invention, a cross section can be taken at line AA, and a cross section can be taken at line BB. A top view of each cross section can be obtained by an electron microscope, a scanning electron microscope, and other microscopes. For example, a top view of a cross section taken at section AA can be compared with a top view taken at section BB. The number of microfibers, the number of nanoparticles, or both in samples of the same two-dimensional size can be evaluated and compared. In addition, imaging techniques can be used on three-dimensional samples. These techniques can be used to evaluate the orientation and other characteristics of the fibers. These techniques can be used to determine that the nanoparticles have been deposited into a certain depth of the substrate, have been substantially deposited across most of the substrate, substantially across the entire depth, or across a certain depth of the substrate.

[0174] In other embodiments, nanoparticles can be added to the substrate from the first and second surfaces 816, 818. In these embodiments, the surface density or "addition amount" at the first and second surfaces 816, 818 can be substantially equal to each other, or they can be different depending on the application. In these embodiments, the surface density or "addition amount" present in the middle of the substrate is lower than the surface density or "addition amount" at the surfaces 816, 818. For example, the surface density in the middle of the substrate can be about 75% of the area density of the surfaces 816, 818, or can be about 50%, 40%, or 25%. Fig.18 A filter product 900 is shown, which includes a filter medium 910 of nonwoven material, the filter medium 910 including fibers 922 and nanoparticles 920 dispersed in at least a portion of the filter medium 910. As shown, the filter medium 910 has a first upper surface 912 and a second lower surface 914. The nanoparticles have been dispersed through the upper surface 912 so that they extend beyond the upper surface 912 and into the filter medium 910 to a certain depth, as described above. The filter product 900 also includes a support layer 930, which can be any suitable support layer known in the art, such as a substantially rigid polymer that provides support for the filter medium 910, or an open membrane having a plurality of pores for gas or fluid to pass through (as described above).

[0175] The fiber of the nonwoven substrate for forming composite material disclosed herein can be formed using known methods, such as meltblowing, spunbonding or above-mentioned other methods.The cross section of the fiber envisioned can have various shapes, including but not limited to circular, kidney bean-shaped, dog-bone-shaped, trilobal, barbell-shaped, bow tie-shaped, star-shaped, Y-shaped, etc. These shapes and / or other conventional shapes can be used together with embodiment to obtain desired performance characteristics.The fiber in the substrate is connected to each other by thermal bond, chemical bond, mutual entanglement, use adhesive (such as adhesive) etc.

[0176] The fibers of the nonwoven substrate can be man-made fibers or natural fibers. Suitable materials for the fibers include, but are not limited to, polypropylene, polyester (PET), PEN polyester, PCT polyester, polypropylene, PBT polyester, copolyamide, polyethylene, high density polyethylene ("HDPE"), LLDPE, cross-linked polyethylene, polycarbonate, polyacrylate, polyacrylonitrile, polyfumaronitrile, polystyrene, styrene maleic anhydride, polymethylpentene, cycloolefin copolymers or fluorinated polymers, polytetrafluoroethylene, perfluoroethylene and hexafluoropropylene or copolymers (such as P(VDF-TrFE)) or terpolymers (such as P(VDF- TrFE-CFE)), propylene, polyimide, polyetherketone, cellulose ester, nylon and polyamide, polymethacrylic acid, poly(methyl methacrylate), polyoxymethylene, polysulfonate, acrylic acid, styrenated acrylic acid, pre-oxidized acrylic acid, fluorinated acrylic acid, vinyl acetate, vinyl acrylic acid, ethylene vinyl acetate, styrene-butadiene, ethylene / vinyl chloride, vinyl acetate copolymer, latex, polyester copolymer, carboxylated styrene acrylic or vinyl acetate, epoxy resin, acrylic copolymer, phenolic resin, polyurethane, cellulose, styrene or any combination thereof. Other conventional fiber materials are contemplated.

[0177] The fibers of the nonwoven substrate can include fibers of different sizes, the diameter of the fibers being generally in the range of about 1 to 1000 microns, and the length being in the range of about half an inch to three inches. The fibers can be configured as gradient density media, wherein the pore size decreases from the upper surface (upstream) to the lower surface (downstream) of the filter to improve capture efficiency and dust holding capacity. This configuration also allows different numbers of nanoparticles to be dispersed into filter media of different depths. For example, the upstream side of the filter medium can have a maximum fiber size to allow more void space and a greater nanoparticle density, while the downstream side of the filter medium has fibers of smaller sizes to provide a lower nanoparticle density. Alternatively, the structure can be reversed to provide a higher density of nanoparticles in the downstream portion of the filter medium.

[0178] The fibers of the nonwoven substrate, as part of the composite material, can be connected to each other by thermal bonding, chemical bonding or mutual entanglement. Bicomponent fibers can be used, especially in mechanical filtration, and these fibers are formed by extruding two polymers from the same spinneret, and both polymers are contained in the same filament. Suitable materials for bicomponent fibers include, but are not limited to, polypropylene (PP) / polyethylene (PE), polyethylene terephthalate (PET) / polypropylene (PP), etc.

[0179] In some embodiments, the substrate may comprise a "high loft" nonwoven material comprising spunbond or through-air bonded carded nonwoven fibers. As used herein, the term "high loft" means that the volume of the void space is greater than the volume of the total solids. In through-air bonded carded nonwoven fibers, the loft of the substrate can be controlled in various ways known to those skilled in the art. For example, the loft can be increased by applying a small compressive force to the medium during the bonding process. In another example, the high loft nonwoven material can be produced with fibers having a larger thickness (e.g., a thickness greater than 3 denier, such as 5 denier or greater, 6 denier or greater) (discussed in more detail below). In other embodiments, the loft can be increased by using different biocomponent fibers, such as Fig.24C shown and discussed in more detail below.

[0180] The fiber of nonwoven substrate can have the thickness suitable for application.In some embodiments, at least one dimension of fiber is about 1 to about 10,000 micron or about 1 to about 1,000 micron or about 10 to 100 micron range.The thickness of fiber can also be measured with denier, and denier is the measurement unit of the mass density of fiber linearity.In some embodiments, the linear density of fiber can be about 1 denier to about 10 denier.Nanoparticle is at least one dimension about 1 to about 1,000 nanometer or about 1 to about 100 nanometer range fiber.The size of above-mentioned fiber and nanoparticle can be diameter or width, specifically depending on the shape of fiber or nanoparticle.

[0181] For gas filters, such as pleated or non-pleated air filters, the linear density of the fibers can range from about 1 denier to about 10 denier. The filter media can contain fibers having the same or different linear densities.

[0182] The linear density of the fibers in air filters is typically about 3 deniers or less to ensure that the fibers are small enough to capture pollutants passing through the filter. Applicants have unexpectedly discovered that by using nanoparticles dispersed in the filter media, the fibers can have a greater linear density, for example, greater than 3 deniers. This is because the nanoparticles provide significant filtering capabilities. In some cases, the linear density of the fibers can be greater than 3 deniers, 5 deniers or greater, 6 deniers or greater, or as large as 7-10 deniers.

[0183] Applicants have also discovered that in some applications, fibers having a linear density greater than that used in conventional filters (e.g., greater than about 3 denier) provide more open space or pores within the filter media, which allows a greater density of nanoparticles to be dispersed therein. Although this may be counter-intuitive to one skilled in the art, Applicants have discovered that fibers having a greater linear density incorporating nanoparticles actually improve the overall efficiency of the filter.

[0184] In certain embodiments, the filter medium may include at least two different fiber thicknesses or linear densities to provide at least two different filter layers in the same filter medium. For example, in some cases, a portion of the filter medium will include fibers having a density greater than 3 deniers, for example, 5 deniers or greater or 6 deniers or greater. Another portion of the filter medium will contain fibers having a more standard linear density (3 deniers or less). This double-layer filter medium creates a first filter portion and a second filter portion, the first filter portion mainly using nanoparticles with a high density in fibers of greater thickness to filter pollutants; the second filter portion mainly using fibers with a lower linear density to filter pollutants, although the two portions may include nanoparticles dispersed throughout the fibers. In certain embodiments, the filter medium may include three or more separate portions or layers, each with a different range of denier fibers.

[0185] Fig.19 Another filtration product 940 is shown that includes a filter media 910 of a nonwoven material including fibers 922 and nanoparticles 920 dispersed in a portion of the filter media 910. In this embodiment, the product 940 includes a scrim layer 950 bonded to a support layer 930.

[0186] Fig. 20 A dual layer filtration product 960 is shown, which includes a first filter medium and a second filter medium 962, 964 bonded to each other. As shown, nanoparticles 920 have been dispersed in a certain depth of each filter medium 962, 964. In this embodiment, the nanoparticles 920 have been dispersed through the inner surface 966, 968 of the filter medium 962, 964. In another embodiment (not shown), the nanoparticles are dispersed through the outer surface 970, 972 of the filter medium 962, 964. In yet another embodiment, the nanoparticles 920 can be deposited on the inner surface 966 of the medium 962 and the outer surface 972 of the medium 964. Fig.19 and 20 Similar filtration products can incorporate composite materials with open-pore polymer sheets, or any other substrate materials mentioned herein. Filter products with combinations of composite materials with different substrates can be used.

[0187] Fig.21A device for incorporating nanoparticles into one or more fiber streams in, for example, a fiber spinning process is shown. In one such embodiment, the nanoparticles are dispersed between two meltblown dies where molten polymer is pushed through small holes to make fibers. When the nanoparticles meet the fibers while they are still sticky, they mechanically entangle with the fibers and thermally bond to the fibers. Therefore, in some embodiments, no additional bonding process is required.

[0188] like Fig.21 As shown, the apparatus 1600 for forming a fibrous nonwoven structure comprises a fiberizing system 1610 similar to one of the above-described systems and devices. The fiberizing system 1610 comprises a nozzle 1620 or similar device for dispersing individual nanoparticles into a first stream 1630. The apparatus 1600 further comprises a system for generating one or more fiber streams that will be combined with the single nanoparticle stream 1630. The system may comprise any system known in the art, such as spunbonding, carding, extrusion, and the like.

[0189] In one example, the system can include a spunbond line, in which filaments are formed by spinning molten polymer and stretching the molten filaments. The fiber bundles of the filaments are separated and spread, and then layered on a net to form a web. The fibers are bonded in the form of sheets by thermal bonding and embossing. The first stream 630 can be introduced, for example, before the attenuation zone or before the bonding (consolidation) process.

[0190] In another embodiment, the system can include two carding machines arranged in series with each other. The first stream 1630 can be introduced at any point after the first carding line and before the second carding line, so that the nanoparticles are sandwiched between the two carded fiber webs. Afterwards, all fibers (including the nanoparticles) are bonded together in a hot air bonding oven (the nanoparticles are thermally interlocked).

[0191] In another embodiment, the device comprises a first feeder and a second feeder, such as a hopper 1640, 1642, which is coupled to a first extruder and a second extruder 1650, 1652. For example, each extruder can include an extrusion screw (not shown) driven by a conventional drive motor (not shown). When the polymer is advanced through the extruder 1650, 1652, the polymer is gradually heated to a molten state due to the drive motor rotating the extrusion screw. Thermoplastic polymers are heated to a molten state and can be completed in multiple discrete steps, when they advance to two melt-blown dies 1660, 1662 through the discrete heating zones of the extruders 1650, 1652, respectively, their temperature gradually increases. Melt-blown dies 1660, 1662 can be another heating zone, in which the temperature of the thermoplastic resin is maintained at a higher level for extrusion.

[0192] Each meltblowing die 1660, 1662 is configured so that the two attenuating air streams of each die converge to form a single air stream that entrains and attenuates the molten strands as they flow from the small holes or orifices 1672 in the meltblowing die. The molten strands are attenuated into fibers or, depending on the degree of attenuation, into microfibers, which have a relatively small diameter, typically smaller than the diameter of the orifices 1672. Thus, each meltblowing die 1660, 1662 has a corresponding single primary air stream 1680, 1690 containing entrained and attenuated polymer fibers.

[0193] The primary air streams 1680, 1690 containing polymer fibers are aligned to converge at the forming zone 1700. In addition, at the forming zone 1030, the first stream 630 of individual nanoparticles is added to the two primary air streams 1680, 1690 of thermoplastic polymer fibers or microfibers. The introduction of the individual nanoparticles into the two primary air streams 1680, 1690 of fibers is intended to produce a distribution of secondary fibrous material 1032 in the combined primary air streams 1680, 1690 of fibers. This can be achieved by merging the first stream 1630 of individual nanofibers between the two primary air streams 1680, 1690 so that all three air streams converge in a controlled manner.

[0194] Examples of suitable meltblowing dies that can be used to produce nonwoven materials are discussed in more detail in U.S. Patent Nos. 6,972,104, 8017534, and 7772456, and U.S. Patent Application No. US20200216979A1, the complete disclosures of which are incorporated herein by reference in their entirety for all purposes.

[0195] Figures 24A-24C Various examples of biocomponent fibers that can be used with the nonwoven substrate materials disclosed herein are shown. Fig.24A A fiber 60 is shown having a core fiber 62 and a surrounding sheath fiber 64. In this embodiment, the core 62 is substantially concentric with the sheath. Fig. 24B A biocomponent fiber 70 is shown having first and second fibers 72, 74 arranged side-by-side with one another. Fig.24C A biocomponent fiber 80 is shown having a core fiber 82 and a sheath fiber 84. In this embodiment, the core 82 is not concentric with respect to the longitudinal axis of the sheath 84, which increases the overall loft of the biocomponent fiber. Of course, other configurations are possible. For example, the core can include shapes other than circular, such as dog-bone, square, triangle, diamond, etc. Alternatively, the fiber can include multiple cores, or it can be divided into three, four, or more quadrants.

[0196] Embodiment 1 is a polymer sheet comprising at least one polymer layer and a plurality of nanoparticles disposed within the polymer layer, the polymer layer having one or more pores for gas or liquid to flow therethrough; wherein at least one dimension of the nanoparticles is less than 1 micron.

[0197] Embodiment 2 is the sheet of embodiment 1, wherein the polymer layer has a first surface and a second surface opposite to the first surface, wherein at least a portion of the nanoparticles are arranged between the first surface and the second surface. Embodiment 3 is the sheet of any one of embodiments 1 to 2, wherein the polymer layer comprises at least one fold to form wrinkles in the sheet.

[0198] Embodiment 4 is the sheet of any one of embodiments 1 to 3, wherein the polymer layer is an extruded film. Embodiment 5 is the sheet of any one of embodiments 1 to 4, wherein the pores comprise voids or perforations. Embodiment 6 is the sheet of any one of embodiments 1 to 5, wherein the pores are in the shape of hexagons, squares, or diamonds.

[0199] Embodiment 7 is the sheet of any one of embodiments 1 to 6, further comprising a plurality of wrinkles across the surface of the polymer layer. Embodiment 8 is the sheet of any one of embodiments 1 to 7, wherein the polymer layer is selected from the group consisting of polypropylene film, high-density polyethylene film, and polylactic acid film. In any embodiment disclosed herein, the polymer sheet comprises at least one polymer layer and a plurality of nanoparticles arranged in the polymer layer, the polymer layer having one or more holes for gas or liquid to flow therethrough; wherein at least one dimension of the nanoparticles is less than 1 micron; further wherein the holes comprise pores or perforations; and further wherein the polymer layer is selected from the group consisting of polypropylene film, high-density polyethylene film, and polylactic acid film.

[0200] Embodiment 9 is the sheet material of any one of embodiments 1 to 8, further comprising a net, mesh, fabric, knit or braid. Embodiment 10 is the sheet material of any one of embodiments 1 to 9, wherein the polymer layer is a substantially rigid support layer for a gas filter.

[0201] Embodiment 11 is the sheet material of any one of embodiments 1 to 10, wherein the polymer layer is a flexible surface layer for use in a face mask. Embodiment 12 is the sheet material of any one of embodiments 1 to 11, wherein the polymer layer is a flexible surface layer for use in a finger bandage pad.

[0202] Embodiment 13 is the sheet of any one of embodiments 1 to 12, wherein the polymer layer is coextruded to form a tacky adhesive layer.

[0203] Embodiment 14 is the sheet material of any one of embodiments 1 to 13, wherein the nanoparticles form a gradient within the polymer layer such that the density of the nanoparticles decreases from the first surface to the second surface. Embodiment 15 is the sheet material of any one of embodiments 1 to 14, wherein the nanoparticles are substantially uniformly dispersed throughout the polymer layer.

[0204] Embodiment 16 is the sheet of any one of embodiments 1 to 15, wherein the nanoparticles are isolated within the fluid and dispersed through the first surface of the polymer layer.

[0205] Embodiment 17 is the sheet of any one of embodiments 1 to 16, wherein the polymer layer comprises fibers having an electrostatic charge. In any of the embodiments disclosed herein, the polymer sheet comprises at least one polymer layer and a plurality of nanoparticles disposed within the polymer layer, the polymer layer having one or more pores for gas or liquid to flow therethrough; wherein at least one dimension of the nanoparticles is less than 1 micron; further wherein the pores comprise pores or perforations; and further wherein the polymer layer, the nanoparticles, or both have an electrostatic charge.

[0206] Embodiment 18 is the sheet of any one of embodiments 1 to 17, wherein the nanoparticles are selected from the group consisting of carbon fibers, glass fibers, polypropylene fibers, nylon fibers, polylactic acid fibers, and combinations thereof.

[0207] Embodiment 19 is the sheet of any one of embodiments 1 to 18, further comprising a binder within the polymer layer to bind the nanoparticles to the polymer layer. Embodiment 20 is the sheet of any one of embodiments 1 to 19, further comprising a binder, wherein the binder comprises a material selected from the group consisting of starch, dextrin, guar gum, PVOH, and a synthetic resin.

[0208] Embodiment 21 is a gas filter comprising a filter medium; and a substantially rigid support layer bonded to the filter medium, wherein the support layer comprises fibers and a plurality of nanoparticles disposed within the support layer, wherein at least one dimension of the nanoparticles is less than 1 micron. Embodiment 22 is the gas filter of embodiment 21, wherein the nanoparticles are configured to filter contaminants passing through the support layer.

[0209] Embodiment 23 is the gas filter of any one of embodiments 21 to 22, wherein the support layer comprises at least one extruded polymer film having one or more pores for gas or liquid to flow therethrough. Embodiment 24 is the gas filter of any one of embodiments 21 to 23, wherein the polymer film has a first surface and a second surface opposite to the first surface, wherein at least a portion of the nanoparticles are disposed between the first and second surfaces.

[0210] Embodiment 25 is the gas filter of any one of embodiments 21 to 24, wherein the polymer film comprises at least one fold to form pleats within the sheet.

[0211] Embodiment 26 is the gas filter of any one of embodiments 23 to 25, wherein the pores comprise pores or perforations. Embodiment 27 is the gas filter of any one of embodiments 23 to 26, wherein the pores are in the shape of hexagons, squares, or diamonds.

[0212] Embodiment 28 is the gas filter of any one of embodiments 21 to 27, further comprising a plurality of pleats extending across the filter media surface.

[0213] Embodiment 29 is the gas filter of any one of embodiments 23 to 28, wherein the polymer membrane is selected from the group consisting of polypropylene membrane, high-density polyethylene membrane, and polylactic acid membrane.

[0214] Embodiment 30 is the gas filter of any one of embodiments 21 to 29, further comprising a mesh, a net, a fabric, a knit, or a braid.

[0215] Embodiment 31 is the gas filter of any one of embodiments 21 to 30, wherein the nanoparticles are isolated within the fluid and dispersed through the first surface of the filter media.

[0216] Embodiment 32 is the gas filter of any one of embodiments 21 to 31, wherein the support layer comprises fibers having an electrostatic charge. In any of the embodiments disclosed herein, the support layer, the nanoparticles, or both have an electrostatic charge.

[0217] Embodiment 33 is the gas filter of any one of embodiments 21 to 32, wherein the nanoparticles are selected from the group consisting of carbon fibers, glass fibers, polypropylene fibers, nylon fibers, polylactic acid fibers, and combinations thereof.

[0218] Embodiment 34 is the gas filter of any one of embodiments 21 to 33, further comprising a binder for bonding the nanoparticles to the support layer. Embodiment 35 is the gas filter of any one of embodiments 21 to 34, further comprising a binder, wherein the binder comprises a material selected from the group consisting of starch, dextrin, guar gum, PVOH, and synthetic resin.

[0219] Embodiment 36 is a composite material comprising a substrate having pores within an internal structure; and a plurality of nanoparticles within the internal structure of the substrate, at least one dimension of the nanoparticles being less than 1 micron; and wherein the nanoparticles form a gradient within the substrate such that the density of the nanoparticles decreases from a first surface of the substrate to an opposing second surface. Embodiment 37 is the composite material of embodiment 36, wherein the substrate comprises a fibrous material.

[0220] Embodiment 38 is the composite material of embodiment 37, wherein the fibrous material comprises a plurality of microfibers, the microfibers having a size of 1 micron or greater.

[0221] Embodiment 39 is the composite material of any one of embodiments 36 to 38, wherein the microfibers are formed in a process selected from the group consisting of a spunbond process, a meltblowing process, and an electrospinning process.

[0222] Embodiment 40 is the composite material of any one of embodiments 36 to 39, wherein the nanoparticles extend a distance of about 1 mm to about 3 mm below the outer surface.

[0223] Embodiment 41 is an air filter having the composite material of any one of embodiments 36 to 40.

[0224] Embodiment 42 is a liquid filter having the composite material of any one of embodiments 36 to 41.

[0225] Embodiment 43 is a face mask having the composite material of any one of embodiments 36.

[0226] Example 1

[0227] A microfiber substrate of bicomponent fibers is provided in the form of a roll, having an inner circular portion of polyester and an outer concentric portion of HDPE. In a roll-to-roll process, the substrate is sprayed with an adhesive and nanofibers or nanoparticles of biosoluble glass fibers are deposited. The nonwoven product is then placed in an oven for heating, and the cooled nonwoven product is collected onto another roll.

[0228] According to the following Figure 12-16 The nanoparticles were deposited by the process described in . In the experiments, biosoluble glass nanofibers were used. The nanofibers had a diameter of about 700 nanometers and a length of about 500 micrometers. In the following examples, a carded hot air bonded nonwoven made of bicomponent fibers was used as the substrate:

[0229] Flat sheet filter media samples were tested at a filtration velocity of 110 fpm. Sample size was 12" x 12". NaCl salt particles ranging from 0.3 to 10 microns were used as the contaminant.

[0230] Example 2

[0231] A carded nonwoven made of 3-denier PET / PE bicomponent fibers was used as a substrate. A composition comprising water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzene sulfonate, lauramine oxide, and ammonium hydroxide was used as a binder. Different nanofiber addition amounts were controlled by adjusting the line speed.

[0232] Table 1

[0233]

[0234] This example shows that by controlling the amount of nanoparticles added, the MERV rating can be increased from MERV 7 to MERV 13.

[0235] Example 3

[0236] A high loft hot air bonded carded nonwoven with 5 denier bicomponent fibers was used as the substrate. A typical starch adhesive was diluted and sprayed before nanofiber deposition. As the solvent evaporated and dried under an IR heater, the starch fully bonded the nanofibers.

[0237] Table 2

[0238]

[0239] Example 4

[0240] Use spunbond or meltblown media as a substrate, wherein nanoparticles are incorporated into the substrate after IPA discharge, as described herein. Spunbond fibers are made of a molten polymer that is spun and stretched to produce filaments. The average basis weight of the substrate is about 90gsm, and the average thickness is about 0.57mm. Use a base sample without any nanoparticles incorporated. Prepare 4 separate samples, which include nanoparticles incorporated into the substrate, as described herein. In sample 2, nanoparticles are incorporated into meltblown fibers after IPA discharge. In samples 1, 3, and 4, nanoparticles are incorporated into spunbond fibers after IPA discharge. The test results are shown in Table 3 below.

[0241] Table 3

[0242] sample# Substrate PD E1 E2 E3 MERV 1 CAB81(Spunbond) 0.41 96% 100% 100% 16 2 CAB81(meltblown) 0.24 75% 98% 100% 14 3 CAB81(Spunbond) 0.40 92% 100% 100% 15 4 CAB81(Spunbond) 0.17 48% 87% 99% 12 Base CAB81(Spunbond) 0.07 9% 46% 90% 9

[0243] As shown, in all three particle groups, the efficiency of the filter media samples incorporating nanoparticles was higher than that of the base samples, and the efficiency of the E2 and E3 particle groups was significantly improved. Using nanoparticles, the overall MERV rating of the samples increased from MERV 7 (base sample) to MERV 12 to MERV 16. The pressure drop of the base sample without nanoparticles was 0.07 inches of water column. The pressure drop of samples 1-4 increased slightly, ranging from 0.17 to 0.41 inches of water column. In sample 2, where nanoparticles were incorporated into meltblown fibers, the MERV rating was 14 and the pressure drop was 0.24 inches of water column.

[0244] Example 5

[0245] A 5 denier hot through bonded carded fiber was used as the substrate. A base sample without nanoparticles incorporated was used. Two separate samples were prepared that included nanoparticles incorporated into the substrate as described herein. The test results are shown in Table 4 below.

[0246] Table 4

[0247] sample# Substrate PD E1 E2 E3 MERV Base 5D carded fiber 0.03 -1% 2% 38% 6 1 5D carded fiber 0.31 57% 90% 98% 13 2 5D carded fiber 0.33 61% 92% 98% 13

[0248] As shown, in all three particle groups, the efficiency of the filter media samples incorporating nanoparticles was significantly improved over the base samples. The use of nanoparticles increased the overall MERV rating of the samples from MERV 6 (base sample) to MERV 13. The pressure drop of the base sample without nanoparticles was 0.03 inches of water column. The pressure drop of samples 1 and 2 increased slightly, ranging from 0.31 to 0.33 inches of water column.

[0249] Example 6

[0250] Meltblown fibers were used as substrates. The average basis weight of the substrate was about 24 gsm and the average thickness was about 0.4 mm. A base sample without nanoparticles or adhesives (e.g., PVOH) was used. Sample 1 included meltblown fibers with the tape side facing up. PVOH was sprayed on the fibers, but nanoparticles were not incorporated. Sample 2 included meltblown fibers with the velvet side facing up. PVOH was sprayed on the fibers, but nanoparticles were not incorporated. Sample 3 included meltblown fibers with PVOH sprayed thereon, and nanoparticles were incorporated into the fibers, as described herein. The test results are shown in Table 5 below.

[0251] Table 5

[0252] sample# Substrate PD E1 E2 E3 MERV Base Meltblown 0.35 82% 96% 99% 14 1 Meltblown 0.38 68% 88% 93% 13 2 Meltblown 0.41 78% 95% 97% 14 3 Meltblown 1.02 92% 99% 99% 15

[0253] As shown, in all three particle groups, especially in the E1 particle group, the efficiency of sample 3 incorporating nanoparticles increased compared to the other three base samples. The overall MERV rating of sample 3 increased from MERV 13 or 14 (base samples) to MERV 15 (using nanoparticles). The PVOH added to samples 2 and 3 did not significantly increase the pressure drop (i.e., 0.35 for the base sample, 0.38 and 0.41 for samples 1 and 2). The pressure drop of sample 3 did increase from about 0.40 inches of water column to about 1 inch of water column. In sample 3, incorporating nanoparticles into the meltblown fiber, the MERV rating was 15 and the pressure drop was 1.02 inches of water column.

[0254] Example 7

[0255] 5 denier hot through bonded carded fibers were used as the substrate. A base sample without nanoparticles was used. Seven additional samples were prepared, which included 5 denier carded fibers with nanoparticles incorporated into the substrate, as described herein. The test results are shown in Table 6 below.

[0256] Table 6

[0257]

[0258]

[0259] As shown, the seven samples incorporating nanoparticles had higher efficiencies than the base samples in all three particle groups, especially in the E2 and E3 particle groups. The overall MERV rating increased from MERV 6 (base samples) to MERV 7 to MERV 13 (with nanoparticles). The pressure drop only increased from 0.03 inches of water column to a maximum of 0.32 inches of water column.

[0260] Example 8

[0261] High loft spunbond fibers were used as substrates in continuous fiber production lines. This test included two different versions: 205-6 and 205-2, in which the settings on the continuous fiber production line were changed to produce two substrates with different weights and thicknesses. Each version (205-6 and 205-2) used a base sample without nanoparticles incorporated. Six additional samples were prepared, which included 205-6 and 205-2 fibers and nanoparticles incorporated into the substrate, as described herein. The test results are shown in Table 7 below.

[0262] Table 7

[0263] sample# Substrate PD E1 E2 E3 MERV Base 205-6 0.04 0% 9% 43% 6 Base 205-2 0.04 0% 8% 37% 6 1 205-6 0.86 88% 98% 99% 15 2 205-2 0.48 79% 96% 99% 14 3 205-6 0.87 82% 97% 99% 14 4 205-2 0.42 61% 90% 98% 13 5 205-6 0.78 79% 97% 99% 14 6 205-2 0.23 44% 79% 96% 11

[0264] As shown, in all three particle groups, the six samples incorporating nanoparticles showed significant improvements in efficiency over the base samples. The overall MERV rating increased from MERV 6 (base samples) to MERV 11 to MERV 14 (with nanoparticles). The pressure drop only increased from 0.04 inches of water column to a maximum of 0.87 inches of water column. The pressure drop in the 205-2 sample only increased to a maximum of 0.48 inches of water column.

[0265] Example 9

[0266] Spunbond and meltblown fibers were used as substrates. For spunbond fibers, the average basis weight of the substrate was about 70 gsm, while for meltblown fibers, the average basis weight of the substrate was about 24 gsm. The average thickness of the substrate was about 0.75 mm. A base sample without nanoparticles was used. Five additional samples were prepared, including spunbond and meltblown fibers and nanoparticles incorporated into the fibers, as described herein. In samples 1-3, nanoparticles were sprayed onto meltblown fibers. In samples 4 and 5, nanoparticles were sprayed onto spunbond fibers. In addition, in samples 1 and 2, the adhesive PVOH was not sprayed onto the substrate. PVOH was sprayed onto samples 3-5. The test results are shown in Table 8 below.

[0267] Table 8

[0268] sample# Substrate PD E1 E2 E3 MERV Base Spunbond+MB 0.07 2% 17% 29% 5 1 Spunbond+MB 0.41 100% 100% 100% 16 2 Spunbond+MB 0.56 100% 100% 100% 16 3 Spunbond+MB 0.26 99% 100% 100% 16 4 Spunbond+MB 0.4 100% 100% 100% 16 5 Spunbond+MB 0.17 97% 100% 100% 16

[0269] As shown, in all three particle groups, the five samples incorporating nanoparticles showed a significant improvement in efficiency over the base samples. The overall MERV rating increased from MERV 5 (base sample) to MERV 16 (with nanoparticles). The pressure drop only increased from 0.07 inches of water column to a maximum of 0.56 inches of water column. In samples 3-5 (PVOH sprayed onto the substrate), the pressure drop only increased to a maximum of 0.4 inches of water column.

[0270] Example 10

[0271] 5 denier hot air bonded carded glass fiber was used as the substrate. A base sample without nanoparticles was used. Three additional samples were prepared, which included 5 denier carded glass fibers and nanoparticles incorporated therein. The test results are shown in Table 9 below.

[0272] Table 9

[0273] sample# Substrate PD E1 E2 E3 MERV Base 5D carded fiber 0.03 -1% 2% 38% 6 1 5D carded fiber 0.27 59% 91% 99% 13 2 5D carded fiber 0.18 45% 83% 98% 12 3 5D carded fiber 0.24 54% 89% 99% 13

[0274] As shown, in all three particle groups, the three samples incorporating nanoparticles showed a significant improvement in efficiency over the base samples. The overall MERV rating increased from MERV 6 (base samples) to MERV 12 or MERV 13 (with nanoparticles). The pressure drop only increased from 0.03 inches of water column to a maximum of 0.27 inches of water column.

[0275] Embodiment 11

[0276] A fiber mixture of 5 denier and 7 denier hot air bonded combed glass fibers was used as the substrate. The medium was hot air bonded. A base sample without nanoparticles was used. Nineteen additional samples were prepared, which included a fiber mixture of 5 denier and 7 denier combed glass fibers and nanoparticles incorporated therein. The test results are shown in Table 10 below.

[0277] Table 10

[0278] sample# Substrate PD E1 E2 E3 MERV Base 5D / 7D Combing 0.03 -1% 2% 38% 6 1 5D / 7D Combing 0.15 37% 64% 95% 10 2 5D / 7D Combing 0.21 33% 70% 92% 11 3 5D / 7D Combing 0.17 42% 80% 98% 11 4 5D / 7D Combing 0.25 47% 82% 96% 12 5 5D / 7D Combing 0.20 48% 84% 98% 12 6 5D / 7D Combing 0.22 49% 84% 98% 12 7 5D / 7D Combing 0.23 53% 85% 97% 13 8 5D / 7D Combing 0.23 53% 87% 98% 13 9 5D / 7D Combing 0.23 54% 88% 98% 13 10 5D / 7D Combing 0.27 54% 88% 98% 13 11 5D / 7D Combing 0.28 54% 87% 98% 13 12 5D / 7D Combing 0.24 56% 89% 98% 13 13 5D / 7D Combing 0.26 56% 88% 98% 13 14 5D / 7D Combing 0.25 57% 90% 98% 13 15 5D / 7D Combing 0.27 57% 89% 98% 13 16 5D / 7D Combing 0.28 57% 89% 98% 13 17 5D / 7D Combing 0.28 58% 90% 98% 13 18 5D / 7D Combing 0.30 58% 90% 98% 13 19 5D / 7D Combing 0.29 59% 89% 98% 13 20 5D / 7D Combing 0.31 65% 94% 99% 13

[0279] As shown, in all three particle groups, all 19 samples incorporating nanoparticles showed significant improvements in efficiency over the base samples. The overall MERV rating increased from MERV 6 (baseline samples) to MERV 10 to MERV 13 (using nanoparticles) (most samples were rated MERV 13). The pressure drop only increased from 0.03 inches of water column to a maximum of 0.31 inches of water column.

[0280] Although these devices, systems and methods have been described in detail herein according to certain preferred embodiments, many modifications and changes may be made thereto by those skilled in the art. Therefore, the foregoing description should not be interpreted as being limited thereto, but rather should be interpreted as including the aforementioned obvious changes, and only limited by the spirit and scope of the following claims.

Claims

1. A polymer sheet comprising: at least one polymer layer having one or more pores for the flow of gas or liquid therethrough; and A plurality of nanoparticles are disposed within the polymer layer, wherein at least one dimension of the nanoparticles is less than 1 micron. 2 . The sheet material of claim 1 , wherein the polymer layer has a first surface and a second surface opposite the first surface, wherein at least a portion of the nanoparticles are disposed between the first surface and the second surface.

3. The sheet of claim 1, wherein the polymer layer comprises at least one fold to form wrinkles in the sheet. The sheet material of claim 1 , wherein the polymer layer is an extruded film.

5. The sheet material of claim 1, wherein the pores comprise voids or perforations. The sheet material according to claim 1 , wherein the holes are in the shape of hexagons, squares or diamonds.

7. The sheet material of claim 1 further comprising a plurality of corrugations extending across a surface of the polymer layer.

8. The sheet material of claim 1, wherein the polymer layer is selected from the group consisting of polypropylene film, high density polyethylene film, and polylactic acid film.

9. The sheet material of claim 1 further comprising a net, mesh, fabric, knit, or braid.

10. The sheet material of claim 1, wherein the polymer layer is a substantially rigid support layer for a gas filter.

11. The sheet material of claim 1 , wherein the polymer layer is a flexible surface layer for a face mask.

12. The sheet material of claim 1, wherein the polymer layer is a flexible surface layer for a finger bandage pad.

13. The sheet material of claim 1 wherein the polymer layers are coextruded to form a tacky adhesive layer.

14. The sheet material of claim 2, wherein the nanoparticles form a gradient within the polymer layer such that a density of the nanoparticles decreases from the first surface to the second surface.

15. The sheet material of claim 1, wherein the nanoparticles are substantially uniformly dispersed throughout the polymer layer.

16. The sheet material of claim 1, wherein the nanoparticles are isolated within a fluid and dispersed through the first surface of the polymer layer.

17. The sheet material of claim 1, wherein the polymer layer comprises fibers having an electrostatic charge.

18. The sheet material of claim 1, wherein the nanoparticles are selected from the group consisting of carbon fibers, glass fibers, polypropylene fibers, nylon fibers, polylactic acid fibers, and combinations thereof.

19. The sheet material of claim 1, further comprising a binder within the polymer layer that binds the nanoparticles to the polymer layer.

20. The sheet material of claim 19, wherein the binder comprises a material selected from the group consisting of starch, dextrin, guar gum, PVOH, and synthetic resins.

21. A gas filter comprising: Filter media; and A substantially rigid support layer is bonded to the filter media, wherein the support layer includes fibers and a plurality of nanoparticles disposed within the support layer, wherein at least one dimension of the nanoparticles is less than 1 micron.

22. The gas filter of claim 21, wherein the nanoparticles are configured to filter contaminants passing through the support layer.

23. The gas filter of claim 21, wherein the support layer comprises at least one extruded polymer film having one or more pores for gas or liquid to flow therethrough.

24. The gas filter of claim 23, wherein the polymer membrane has a first surface and a second surface opposite the first surface, wherein at least a portion of the nanoparticles are disposed between the first surface and the second surface.

25. The gas filter of claim 23, wherein the polymer film comprises at least one fold to form pleats in the sheet.

26. The gas filter of claim 23, wherein the pores comprise pores or perforations.

27. The gas filter of claim 21, wherein the pores are in the shape of a hexagon, a square, or a diamond.

28. The gas filter of claim 21, further comprising a plurality of pleats extending across a surface of the support layer.

29. The gas filter of claim 23, wherein the polymer film is selected from the group consisting of a polypropylene film, a high-density polyethylene film, and a polylactic acid film.

30. The gas filter of claim 21 further comprising a mesh, a net, a fabric, a knit, or a braid.

31. The gas filter of claim 21, wherein the nanoparticles are isolated within a fluid and dispersed through the first surface of the polymer layer.

32. The gas filter of claim 21, wherein the support layer comprises fibers having an electrostatic charge.

33. The gas filter of claim 21, wherein the nanoparticles are selected from the group consisting of carbon fibers, glass fibers, polypropylene fibers, nylon fibers, polylactic acid fibers, and combinations thereof.

34. The gas filter of claim 21, further comprising a binder within the support layer that binds the nanoparticles to the support layer.

35. The gas filter of claim 34, wherein the binder comprises a material selected from the group consisting of starch, dextrin, guar gum, PVOH, and synthetic resin.

36. A composite material comprising: A substrate having pores within its internal structure; a plurality of nanoparticles within the interior structure of the substrate, the nanoparticles having at least one dimension less than 1 micron; and The nanoparticles form a gradient within the substrate such that a density of the nanoparticles decreases from a first surface to an opposite second surface of the substrate.

37. The composite material of claim 36, wherein the substrate comprises a fibrous material.

38. The composite material of claim 37, wherein the fibrous material comprises a plurality of microfibers, the microfibers having a size of 1 micron or greater.

39. The composite material of claim 38, wherein the microfibers are formed in a process selected from the group consisting of a spunbond process, a meltblown process, and an electrospinning process.

40. The composite material of claim 36, wherein the nanoparticles extend a distance of about 1 mm to about 3 mm below the outer surface.

41. A gas filter comprising the composite material of claim 36.

42. A liquid filter comprising the composite material of claim 36.

43. A face mask comprising the composite material of claim 36.